Interconnected macroporous foamed hydrogels enable stable and efficient nitrogen removal in low temperature Anammox systems - Wanqi Liu; Ning An; Yuhan Zhu; Peng Gao; Tingting Liu; Xingrong Yao; Kaiyao Hu; Jun Li; Dongyue Li; Zhaoming Zheng; Zehao Zhang (Water Research, 2027)

Comprehensive study of the tumor immune microenvironment and the prognostic significance of reticulocalbin-1: a pan-cancer analysis - JiangLi Zhao; XuChen Liu; QingYuan Sun; ShuJie Peng; ZhiWei Xue; JunZhi Liu; Bin Huang; JiWei Wang; Chao Li; Ning Yang; Xinyu Wang (Functional & Integrative Genomics, 2026)

Mechanism and engineering evaluation of multi-element removal in lead-bismuth fast reactor concentrate using commercial ion exchange resins - Shiyang Peng; Jiayu Li; Shuang Li; Ning Zhang; Kaiyuan Jiang; Hua Xie (Annals of Nuclear Energy, 2026)

Cropping diversification increases microbial network complexity associated with enhanced soil multifunctionality and resistance to global change - Qian Guo; Peng He; Rui Li; Rong Yang; Jianing Wang; Tengfei Ma; Ning Ling; Lina Zheng; Zhaoming Wang (Soil and Tillage Research, 2026)

A critical review on microalgae-driven wastewater treatment: Dual focus on high-value bioproducts recovery and emerging contaminants removal - Shuli Liu; Jiajun Hua; Yuhong Zhang; Yatong Gao; Xiaohong Han; Yali Liu; Glen T. Daigger; Qi Li; Ning Guo; Zhixin Song; Peng Zhang; Xiane Zhang; et al. (Journal of Environmental Sciences, 2026)

Xylitol-regulated interfacial polymerization enables high-permeance and antifouling nanofiltration membranes for selective surface water purification - Guangchao Li; Yixuan Li; Guangjian Bao; Xinwei Kang; Jianjun Zhu; Yongshan Ma; Ning Wang; Xinyu Zhang; Hong Peng; Xuewu Zhu (Desalination, 2026)

Two new acylated iridoid glycosides with insulin resistance-improving activity from Scrophularia ningpoensis - Wen-Ying Zhou; Yu-Xin Peng; Bi-Qing Zhao; Hong-Yu Jiang; Xi-Ning Sun; Guang-Yun Su; Li Li; Xiao-Jiang Zhou (Phytochemistry Letters, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

Reconstruction of satellite remote sensing AOD considering spatial gap filling and downscaling - Xu Chen; Bowen Meng; Yun Peng; Huiyi Xiao; Bin Zou; Shoutao Zhu; Ning Liu; Shenxin Li; Xin Fang (Atmospheric Environment, 2026)

Methylome and transcriptome profiles reveal the importance of glycometabolism in thermal plasticity of large yellow croaker - Yanfei Yang; Yichen Li; Yidi Wu; Baohua Chen; Ji Zhao; Qiaozhen Ke; Weiqiang Zheng; Yun Li; Tao Zhou; Peng Xu; Ning Li (Aquaculture, 2026)

Landscaping neurodevelopment of attention-deficit hyperactivity disorder - Ningning Liu; Yin-Shan Wang; Zi-Xuan Zhou; Peng Gao; Chongjing Luo; Xinyi Zhang; Ziqing Zhu; Yuan Gao; Fei Ren; Yan Zhu; Li-Zhen Chen; Haimei Li; et al. (Science Bulletin, 2026)

pH-Dependent flotation mechanisms of beryl with dodecylamine: from conventional froth flotation to non-froth aggregate flotation - Jingchao Li; Yangge Zhu; Dashi Lei; Ning Sun; Xiaoliang Zhang; Xiang Li; Xiangyu Peng; Liming Wang; Zeping Feng; Jubin Zhai; Fenghua Ding; Yubin Wang (Minerals Engineering, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

A synergistic piezo-photocatalytic strategy via BaTiO3 heterophase homojunctions for MRSA-infected diabetic wound therapy - Lei Qian; Han Lin; Min Wu; Zheng Fang; Jiawei Li; Yao Han; Jinxia Zhai; Peng Yu; Cairong Xiao; Chengyun Ning (Chemical Engineering Journal, 2026)

Dual-functional nanotherapeutics: A novel approach to siRNA-mediated TNF-α silencing in inflammatory bowel disease - Li Qiao; Xue-Tian Qian; Yi-Gang Zhang; Xia-Feng Peng; Qi Liu; Shi-Qi Chang; Chang Cui; Feng Zhang; Shu-Kui Wang; Ning-Ping Huang (Chemical Engineering Journal, 2026)

Improved soil quality underpins bacterial resistance against rainfall perturbations to mitigate maize yield loss - Yangbo Huai; Yonghua Li; Lu Yang; Peng Ning (Applied Soil Ecology, 2026)

Genetic selection response and genomic basis of resistance to Cryptocaryon irritans in large yellow croaker (Larimichthys crocea) - Yin Li; Ji Zhao; Jiaying Wang; Qiaozhen Ke; Hongshu Chi; Sijing Chen; Yujia Chen; Huasong Weng; Fei Pu; Ning Li; José M. Yáñez; Tao Zhou; et al. (Marine Life Science & Technology, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Mediation effects of thyroid hormones in the associations between essential metal elements and anxiety or depression symptoms in the elderly - Juanhua Li; Wenqi Wang; Yang Peng; Ning Qin; Jiemei Li; Ying Wei; Biwen Wang; Huaicai Zeng; Han Li; Lu Cheng (BioMetals, 2026)

Double-layered soil profile structure in an agro-pastoral ecotone revealed by geochemical characteristics: implications for wind erosion in northern North China - Jian-Yu Liu; Chun-Lei Zha; Zhi-Qiang Yin; Ling Peng; Kai-Ning Lv; Jun Li; Guo-Li Yuan (Environmental Monitoring and Assessment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Internal wave behaviors in the central Andaman Sea observed by a moored buoy - Yuchen Peng; Yanliang Liu; Kuiping Li; Chunlin Ning; Liang Chen; Lina Sun; Chalermrat Sangmanee; Yue Fang (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Transcriptomic Analyses Reveal Intestine and Liver Responses of Large Yellow Croaker (Larimichthys crocea) to Plant Protein Diet - Wei Liu; Peihong Huang; Qiaozhen Ke; Jiaxing Liu; Fei Pu; Peng Xu; Ning Li; Tao Zhou (Marine Biotechnology, 2026)

Integrated Analysis of Physiological, Histological, and Transcriptomic Responses to Transport Density in Schizothorax nukiangensis - Jinlin Wang; Yuting Duan; Dapeng Gu; Hejiao Li; Luo Lei; Ning Wang; Wenjia He; Yinhua Zhou; Rongrong Liao; Mei Peng; Xinyu Liu; Zhaofang Han; et al. (Marine Biotechnology, 2026)

Enhanced net carbon dioxide sink in rice-duckweed system: Evidence from the diurnal flux variation - Weixuan Liu; Ning Gao; Yawei Li; Xiaoyin Liu; Xue Zhou; Yihao Peng; Lili Zhu; Jian Meng; Junzeng Xu (Agriculture, Ecosystems & Environment, 2026)

Non-monotonic regulation of collective dynamics by group size and speed in schooling fish - Junjia Zeng; Ke Xie; Yanfei Yang; Sijing Chen; Gowena Ling Yi Goh; Yacheng Deng; Ning Li; Tao Zhou; Fei Pu; Wenjing Lu; Kuoqiu Yan; Peng Xu (Aquaculture, 2026)

Three new diterpenoids from the aerial parts of Callicarpa macrophylla - Liang Gou; Rong-Shuai Li; Jian-Lin Lai; Yan-Mei Ning; Xue-Ting Ji; Xiong Qiu; Chao Peng; Xiao-Li Li; Xing-Jie Zhang; Wei-Lie Xiao (Natural Product Research, 2026)

Hydrobiogeochemical impacts of water sealing on acid mine drainage in karst regions - Lei Song; Peng Liu; Chao Li; Haili Zhang; Jie Yan; Yuhui Liu; Zengping Ning; Yizhang Liu; Jing Sun; Hefa Cheng; Chengshuai Liu (Journal of Hydrology, 2026)

Identification of the functional food ingredients as novel CD38 inhibitors via pharmacophore model-based molecular docking - Xiaochun Liu; Hongju Li; Xinru Gao; Ning Hou; Chunying Du; Jiajie Li; Fengjiao Wei; Leke Qiao; Senbiao Fang; Peng Wang; Ximing Xu (Food Bioscience, 2026)

Global divergent responses of soil heterotrophic respiration to nitrogen deposition - Peng Guo; Mengyu Miao; Han Zhao; Tian Zuo; Ning Wang; Luna Yan; Zhaowei Li; Tianming Li (CATENA, 2026)

The pivotal regulatory factor circ_0006956 promotes arsenic-induced lung carcinogenesis by enhancing the Warburg effect - Deqing Li; Xiaodong Zhou; Dunyu Cai; Haotian Xu; Xingcai Chen; Shengyi Yuan; Taoran Ning; Xiangyu Dong; Mengyao Li; Qiumei Liu; Ruirui Zhang; Wenyi Peng; et al. (Chemico-Biological Interactions, 2026)

Genetic differentiation and machine learning based SNP marker development in the Cryptocaryon irritans resistant large yellow croaker (Larimichthys crocea) strain - Yin Li; Ji Zhao; Ningyuan Ding; Changliang Zhang; Ning Li; Tao Zhou; Peng Xu (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Managing low C/N municipal wastewater in full-scale IFAS: Interactive effects of acetate dosing and seasonal cooling - Ning Chen; Xiaodong Wang; Shanshan Chen; Peng Xiao; Tao Ma; Xiang Li (Process Safety and Environmental Protection, 2026)

Pennsylvanian (Bashkirian) microbial reefs from Guizhou Province, South China: Characteristics and insights into the middle Carboniferous microbial reef development - Guan-Ming Lai; Yong-Li Zhang; En-Pu Gong; Ning-Feng Du; Wen-Tao Huang; Deng-Hui Chen; Yu Li; De-Peng Li (Palaeoworld, 2026)

Nanocellulose-reinforced deep eutectic solvent-based smart hydrogel sensor for adaptive window regulation and machine learning-assisted low-temperature motion monitoring - Zhenchun Li; Yucong Sun; Jiarui Shen; Rongfeng Ge; Jieli Hua; Zhiyuan Zhao; Ning Li; Yunqi Peng; Jiaqi Hou; Hong Zhang; Lei Wang (Chemical Engineering Journal, 2026)

Integrating Time and Frequency Domain Features of fMRI Time Series for Alzheimer’s Disease Classification Using Graph Neural Networks - Wei Peng; Chunshan Li; Yanhan Ma; Wei Dai; Dongxiao Fu; Li Liu; Lijun Liu; Ning Yu; Jin Liu (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Rapid evaluation of the comprehensive quality of paeonol/cyclodextrin supramolecular complexes using CASSA based on near-infrared spectroscopy combined with artificial intelligence - Bo-yao Zhang; Xin-li Li; Cheng Qian; Si-min Xue; Zhi-tong Zhang; Si-yi Liu; Guo Zhang; Guo-ping Peng; Ning Ding; Yun-feng Zheng (Molecular Diversity, 2026)

Astragaloside IV attenuates cisplatin-induced ototoxicity by preserving mitochondrial function and activating the Nrf2 signaling pathway - Tan Wang; Daquan Wu; Peng Wang; Li Gao; Zhemeng Chen; Xianhui Ning; Xinsheng Huang; Kanglun Jiang (NeuroToxicology, 2026)

A comprehensive flavor evaluation method for drinking water based on flavor rating assessment (FRA) and the flavor wheel, incorporating benchmark referencing and objective weighting - You Lyu; Huan He; Zhen-Ning Luo; Tian-Yang Zhang; Xin-Li Huang; Zhu Peng; Qi Fu; Xin-Bai Jin; Bin Xu (Journal of Water Process Engineering, 2026)

Accumulation pattern, source apportionment and risk assessment of soil heavy metals across diverse land use types: Insights from the northern foothills of Qinling mountains, China - Bingyao Huo; Yanjun Shen; Yibing Ning; Wei Shen; Penghui Ma; Zhijie Jia; Luqing Zhao; Junyan Zhao; Xing Chen; Tao Ding; Sirui Li; Jianbing Peng (CATENA, 2026)

A conservation trade-off: overgrazing by reintroduced Père David’s deer threatens canopy-nesting birds in coastal engineered forests in China - Dawei Wu; Bin Liu; Guoqin Liu; Junjie Peng; Pan Chen; Ning Li; Fang Zhang (Biodiversity and Conservation, 2026)

Coordinated Vessel Arrival Time Prediction and Berth Allocation Optimization for Efficient Port Operations - Peng Fei; Wu Ning; Kecheng Li; Xiyao Xu; Xiumin Chu; Chenguang Liu (Journal of Marine Science and Engineering, 2026)
Uncertainty in vessel arrival times can substantially reduce the efficiency of berth planning in port operations. To address this issue, this study proposes a unified, data-driven, predict-then-optimize framework that explicitly links vessel arrival time (VAT) prediction with downstream continuous berth allocation optimization. In the prediction stage, heterogeneous maritime data, including port call records, AIS trajectories, and vessel physical characteristics, are integrated to construct VAT prediction models. In the optimization stage, the predicted VAT is embedded into a continuous berth allocation problem (BAP) model to support berth scheduling decisions. To better reflect real operations, a two-stage evaluation framework is further developed, in which berth plans generated from estimated arrival times (ETAs) or predicted VATs are re-evaluated under realized actual arrival times while preserving the original temporal and spatial service order. Experimental results show that the proposed framework improves VAT prediction accuracy substantially, reducing the MAE and RMSE from 4.795 h and 7.255 h for the vessel-reported ETAs to 2.844 h and 4.934 h, respectively. More importantly, the predicted-VAT-based BAP consistently outperforms the ETA-based benchmark, yielding an overall 35.96% reduction in objective value across tested scenarios. These findings demonstrate that improved VAT prediction can be effectively translated into meaningful operational gains in berth allocation.

Conjugated organic polymer enables external-sacrificial-agent-free photocatalytic uranium extraction with efficiency boosted by oxygen pre-activation - Xuefeng Tian; Jipeng Li; Xuewen Cao; Jiacheng Zhang; Rui Huang; Peng Lin; Ning Wang; Yihui Yuan (Science Bulletin, 2026)

Impact of organic carbon composition on bacterial community assembly in organic and mineral soil layers under phosphorus addition in a Robinia pseudoacacia plantation - Ahejiang SAILIKE; Yujie LIANG; Rong FU; Hongjian HAO; Rong WANG; Ning PENG; Shicai LI; Zhouchang YU; Fangxin ZHENG; Wei ZHANG; Yangyang LIU; Peizhi YANG; et al. (Pedosphere, 2026)

Phase separation of the redox sensor RCD1 mediates differential ROS signals to regulate plant growth and stress responses - Jingjing Xing; Kaiwen Li; Wenwen Duan; Zhikun Duan; Yu Zhang; Aiyu Guo; Suting Wang; Ning Ding; Yaling Zou; Xiaobin Wei; Xiaoliang Zhao; Junli Zhang; et al. (Molecular Plant, 2026)

Fe/Cu-γ-Al2O3 catalyst for pilot-scale internal circulation Fenton degradation of methyl orange: performance and mechanism - Dekai Fan; Yanran Lin; Peng Zhu; Yingwen Zhang; Bang Yao; Li Chao; Zhuangzhuang Jia; Jianjun Dai; Yingrui Ning; Rong Xiao; Chen Chen; Lei Gao; et al. (Journal of Environmental Management, 2026)

Collaboration of the symbiotic microbiome and host genome during the high altitude adaptation of chickens - Jiaming Jin; Chaoliang Wen; Junying Li; Chunning Mai; Jingwei Yuan; Ping Wang; Da Peng; Yiqiang Zhao; Congjiao Sun; Xueying Ma; Jing Feng; Ning Yang (Science China Life Sciences, 2026)

Increasing phosphorus availability and dynamics enhance soil organic carbon and its sub-pools sequestration as consequence of phosphorus inputs - Yao Liu; Junru Li; Ning Su; Xiangmin Rong; Yuping Zhang; Xianjun Zeng; Jianwei Peng; Gongwen Luo (Soil Ecology Letters, 2026)

Modeling and experimental validation of crack-induced bottom-side erosion effects in buried pipelines - Yan-Ning Wang; Tai-Kai Li; Jing-Rui Peng; Xin-Hao Min; Lin-Shuang Zhao (Tunnelling and Underground Space Technology, 2026)

Valorization of phosphogypsum and silica fume in sustainable cementitious materials: Multi-objective optimization and mechanistic insights - Zilong Zhou; Haoyang Fan; Hang Li; Yanlei Chen; Sheng Zhang; Caiyue Jin; Zhongxi Jiang; Ning Liu; Liwei Peng (Journal of Environmental Management, 2026)

A molecular understanding of the potent health of wholemeal sourdough bread derived from different lactic acid bacterial fermentation - Cheng Chen; Anqi Wang; Haotian Wu; Ming Ning; Peng Yu; Ning Li; Chris Blanchard; Zhongkai Zhou; Weining Huang (Journal of Cereal Science, 2026)

Conservation mulching with plastic film in maize field of arid irrigation region: Agronomic performance, economic, and environmental effects - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Xiao-Yu Lu; Ying Zhu; Meng Hao; Ning Wang; Meng-Ying Li; Xiao-Feng Zhang; Hong-Yan Tao; You-Cai Xiong (Field Crops Research, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Harnessing Intraspecific Dynamics in Strip-Planted Wheat: The Dual Role of Competition in Tiller Mortality and Post-Anthesis Growth - Yu Liu; Yonghua Li; Shuhui Song; Xiaojie Feng; Zhanhong Hao; Songlin Ye; Xinsheng Niu; Guohua Mi; Peng Ning (International Journal of Plant Production, 2026)

Analysis of drag force, deformation and stress distribution of biofouled flexible nets - Songchen Yu; Ning Wang; Hongde Qin; Peng Li (Aquacultural Engineering, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Research on Combustion Strategies for Marine Low-Speed Two-Stroke Direct Injection Ammonia/Diesel Dual Fuel Engines - Ye-Peng Li; En-Zhe Song; Ke-Shuai Sun; Yi-Lin Ning (Journal of Marine Science and Engineering, 2026)
This study investigates the combustion and emission characteristics of a marine low-speed two-stroke engine using diesel-ignited ammonia dual direct injection. Using a validated 3D CFD model, the impact of ammonia blending ratios (Ra) was systematically explored. Results indicate that the strategy of shifting energy from early diesel injection to late ammonia injection physically repositions the combustion phasing. Rather than ammonia delaying the heat release, this late injection strategy avoids the overly early combustion observed at low ammonia concentrations, thereby lowering peak in-cylinder temperatures while maintaining robust work extraction. Consequently, indicated power at the N90 condition increases by 3.5% (to 1689 kW) over the diesel baseline, with a minimum EISFC of 165.5 g/kWh. High-ratio ammonia blending achieves deep decarbonization: at N90, peak CO and soot emissions are reduced by over 90% and 95%, respectively. Additionally, NOx emissions decrease by approximately 70% at N90 compared to the N20 peak, attributed to the thermal DeNOx mechanism. However, the low-temperature environment introduces trade-offs, leading to increased ammonia slip (4 ppm at N90) and elevated N2O emissions (peaking at N70). These findings clarify the mechanisms governing ammonia combustion and provide theoretical support for optimizing zero-carbon marine propulsion systems.

Genomic safety assessment and metabolic modulation by Enterococcus faecium 140,623, a probiotic strain from lactasin tablets: implications for obesity management - Yongqi Gan; Cheng Liu; Xiaorui Zheng; Jun Nong; Lanyan Fan; Peng Xie; Yang Li; Bin Zhu; Ling Ning; Zan Zhang (World Journal of Microbiology and Biotechnology, 2026)

Integrating geometric morphometrics and GWAS to reveal the genetic basis of body shape variation in large yellow croaker (Larimichthys crocea) - Wei Liu; Yuhang Wang; Miaosheng Feng; Jiaying Wang; Junjia Zeng; Yacheng Deng; Fei Pu; Ning Li; Peng Xu (Aquaculture, 2026)

Molecular weight-dependent binding heterogeneity of heavy metals with dissolved organic matter in plateau waters: Insights from EEM-PARAFAC and moving-window - Keli Yang; Mengli Huang; Huacheng Xu; Xin Liu; Tianyuan Chen; Ning Li; Laodong Guo; Jiaoyu Peng; Yaoling Zhang (Journal of Environmental Chemical Engineering, 2026)

RNA-mediated alternative splicing and polyadenylation shape immune responses underlying disease resistance to Pseudomonas plecoglossicida in Larimichthys crocea - Yin Li; Yujia Chen; Yulin Bai; Longyu Chen; Sijing Chen; Ning Li; Peng Xu; Tao Zhou (Fish & Shellfish Immunology, 2026)

Associations of paraben exposures measured by repeated urinary biomarkers with sperm DNA damage and apoptosis - Xiu-Ting Li; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Ning Zhang; Long Ge; Han-Qin Ye; Pan-Pan Chen; et al. (Environmental Research, 2026)

Crosslinked polymer aerogel with multiple binding sites for efficient uranium separation from uranium-containing wastewater - Yaping Jian; Jiacheng Zhang; Xuewen Cao; Jipeng Li; Qin Peng; Xuefeng Tian; Jianfei Du; Yihui Yuan; Ning Wang (Environmental Research, 2026)

From vegetation classification to vegetation zonation: a multi-source modelling framework for evergreen broad-leaved forests in complex terrain - Shiqi Zhang; Peihao Peng; Ning Li; Juan Wang; Xuefeng Peng; Zhaozhi Luo (Environmental Modelling & Software, 2026)

Dual functions of pyrite modified polyethylene carrier in Anammox biofilm: Promoting biofilm growth and enhancing nitrogen removal - Tingting Liu; Dongyue Li; Peng Gao; Yuhan Zhu; Linzhu Du; Xingrong Yao; Wanqi Liu; Kailun Yang; Xingxing Xiong; Ning An; Jiarui Li; Qian Zhao; et al. (Chemical Engineering Journal, 2026)

Microwave-assisted pyrolysis of dyeing sludge: Reaction kinetics, elemental transformation, and heavy metal migration - Dekai Fan; Rong Xiao; Wahab Nasarul; Chunbao Zhou; Yingwen Zhang; Bang Yao; Li Chao; Jianjun Dai; Gul Urooj; Yingrui Ning; Peng Zhu; Chen Chen; et al. (Chemical Engineering Journal, 2026)

An all-in-one programmable Janus membrane with gemini AIE surfactant for integrated bioaerosol management - Saisai Yan; Xiyao Wang; Zishu Wen; Yufeng Guan; Bixiao Cao; Xuanzhe Wang; Ning Du; Yingjie Zhong; Ningning He; Shangyong Li; Peng Sun (Chemical Engineering Journal, 2026)

Innovative utilization of waste printed circuit boards and coal gangue/ash for multifunctional glass-ceramics: structure-property insights via data-driven analysis - Yingwen Zhang; Lei Gao; Li Chao; Bang Yao; Dekai Fan; Chen Chen; Rong Xiao; Yingrui Ning; Peng Zhu; Urooj gul sandilo; Abeanezer Lukas Bassa; Nasarul Wahab; et al. (Chemical Engineering Journal, 2026)

An anisotropic multi-amine-mediated dynamic network for strong, tough, and self-strengthening conductive hydrogel - Qingye Liu; Xiaohui Wang; Wenbo Xu; Xuan Ning; Yu Yang; Peng Li; Yanling Hu; Xiaojun Li; Qingqing Li (Chemical Engineering Journal, 2026)

Nanocarrier-mediated RNAi targeting glutamate decarboxylase synergizes with neonicotinoids for aphid control - Chenxi Liu; Xinyuan Ning; Peng Zhao; Zihan Wei; Yuqing Xie; Lin Zhu; Zhen Li; Xiaoxia Liu (Chemical Engineering Journal, 2026)

Intelligent Control System for Particulate Matter: Real-Time Monitoring and Pollution Source Identification for Enhanced Efficiency - Peng Shi-Tao; Li Long-Chuang; Ye Yin; Hong Ning-ning; Zhang Jing; Chen Zi Jing; Du Hong-Bo (Water, Air, & Soil Pollution, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Integrative Assessment of Interrelated Swimming Performances and their Physiological Basis in Large Yellow Croaker (Larimichthys crocea) - Wei Liu; Junjia Zeng; Jiaxing Liu; Tingsen Jiang; Yacheng Deng; Pengxin Jiang; Yin Li; Ningyuan Ding; Yichen Li; Yujia Chen; Chuan Deng; Haojie Li; et al. (Marine Biotechnology, 2026)

Unraveling shallow landslides in the Qinling Mountains: Novel insights into vegetation-hydrology driven mechanisms - Xing Chen; Yanjun Shen; Yibing Ning; Bailei Shi; Jinyu Zhu; Sirui Li; Zijian Li; You Lyu; Jianbing Peng (Journal of Mountain Science, 2026)

Estimation and simulation on carbon sinks potential of marine aquaculture in China - Peng Li; Xinhao Wu; Dezhi Ning; Yichuan Zhang; Mengru Jiang; Siyi Li; Nan Ma; Jianke Guo (Journal of Geographical Sciences, 2026)

Multi-parameter GNSS monitoring for expansive soil hazards: a case study from coastal Texas - Xiongchuan Chen; Shuangcheng Zhang; Yong Fang; Qingtao Zhang; Lidu Zhao; Peng An; Ning Liu; Qi Liu; Ningkang An; Jun Li; Zhilei Ye (Advances in Space Research, 2026)

Acupuncture as a modulator of microglial polarization and pyroptosis in depression: evidence from a chronic unpredictable mild stress rat model - Xinhong Wu; Zhuoran You; Tiansheng Zhang; Jingyu Zeng; Meng Li; Simin Yan; Jianguo Li; Peng Li; Junliang Shen; Siyu Liu; Muhammad Shahzad Aslam; Jingxuan Li; et al. (Metabolic Brain Disease, 2026)

Nitrogen fertilization simultaneously strengthens soil carbon and nitrogen pools, with implications for productivity gain of double-cropping rice system - Junru Li; Yao Liu; Hao Huang; Ning Su; Qiulong Hu; Xiangmin Rong; Yuping Zhang; Jianwei Peng; Gongwen Luo (Biology and Fertility of Soils, 2026)

Microbial mechanisms underlying differences of methane emissions between urban and rural wetlands - Yuwen Lin; Xinyu Yi; Chen Ning; Yong Li; Yinghe Peng; Shuguang Liu; Changhui Peng; Xiaoyong Chen; Shuailong Feng; Pengpeng Duan; Yan Liu; Juyang Liao (Soil Biology and Biochemistry, 2026)

Analysis of nitrogen removal performance of gel-immobilized cold-acclimated Anammox granules under low temperature and high nitrogen loading rate (NLR) conditions - Linhua Zhang; Jing Zhang; Jun Li; Peng Gao; Jianwei Chen; Dongyue Li; Xingxing Xiong; Sairui Guan; Ning An; Kailun Yang; Tingting Liu; Xingrong Yao; et al. (Process Safety and Environmental Protection, 2026)

Comprehensive investigation of the IKKα gene and TBK1 gene's identification, molecular evolution, and expression profiling in lampreys - Boting Lan; Xinyu Du; Ning Yang; Si Gao; Tiesong Li; Peng Su (Fish & Shellfish Immunology, 2026)

Sulfone site enables H2O2 practical fabrication over metal-free photocatalyst - Zhi-Peng Tao; Lin Liu; Ke-Chao Wang; Chen-Ning Li; Jia-Qi Chu; Zhen-Hui Kang; Zheng-Bo Han (Chemical Engineering Journal, 2026)

Echinacoside Improves Memory Function and Bone Mineral Density in the Aged SAMP8 Mouse Model - Rong Zhou; Ge Tian; Jing Yu; Rui Wang; Ning Peng; Xingzhi Guo; Rui Li (Molecular Neurobiology, 2026)

A dual-mode colorimetric and electrochemical strategy for sensitive detection of PRRSV using imidazole-copper nanozymes - Jing Li; Xiang Lai; Chong Zhang; Yu-Fan Huang; Guo-Bao Ning; Si-Ying Ma; Ao-Xiang Chen; Ming-Rui Li; Guo-Hao Li; Qin Zhao; Can-Peng Li; Hui Zhao (Analytica Chimica Acta, 2026)

Scopolamine exerted antidepressant-like behavioral effects via restoring the synaptic plasticity in CRS-treated mice - Peng-Wei Bi; Si-Rui Sun; Jia-Ning Zhao; Hui-Ying Zhang; Ze Lv; Yong-Yu Yin; Yun-Feng Li (Metabolic Brain Disease, 2025)

Monitoring and determinants analysis of canopy layer urban heat island in China based on both air temperature and apparent temperature - Yuanzheng Li; Chaoqun Ma; Tengbo Yang; Zhifeng Wu; Rui Yao; Guosong Zhao; Xiaojv Ning; Peng Kang (Urban Climate, 2025)

Bioinspired Nacre-layer composite loose nanofiltration membranes: Preparation and performance evaluation - Junpeng Mao; Peng Liu; Ning Tang; Hui Li; Yaxin Gu; Yunwu Yu; Yunxue Liu; Lihua Wang; Ji Cao (Journal of Environmental Chemical Engineering, 2025)

Spatio-temporal heterogeneity of quality attributes and flavors in grass carp (Ctenopharyngodon idella) cubes during deep frying: Key metabolic evidence - Hao Wang; Ning Cui; Bin Peng; Chengwei Yu; Bizhen Zhong; Mingming Hu; Jinlin Li; Zongcai Tu (Food Chemistry, 2025)

Biofilm with a mechanically strengthened character via enhanced cross-links of soybean proteins with short-chain fatty acid-modified starch - Sheng Ke; Gaoheng Li; Anqi Wang; Haotian Wu; Peng Yu; Ming Ning; Padraig Strappe; Bing Wang; Chris Blanchard; Zhongkai Zhou; Guohua Zhao (Food Chemistry, 2025)

Copper sulfide catalysts facilitating zinc sulfide electro-oxidation in aqueous zinc–sulfur batteries - Peng Hei; Guangxu Hu; Lin Yu; Yulai Lin; Xueying Ning; Bo Li; Yuqing Wang; Zhaohui Chen; He Chong; Hao Cheng; Jing Wang; Weibin Cui; et al. (Chemical Engineering Journal, 2025)

Theranostic nanoplatform for triple-negative breast cancer therapy: Autophagy suppression-coordinated siRNA delivery triggers apoptosis, ferroptosis, and pyroptosis via photothermal activation - Guobao Ning; Lishen Yang; Bilian Li; Jianghua Lin; Shufen Li; Fengqi Zhou; Han Chen; Xingye Zheng; Weijie Sun; Hui Zhao; Can-Peng Li (Chemical Engineering Journal, 2025)

Long-term carbon release of peatland soil after permafrost thaw in northmost China - Yunjiang Zuo; Yanyu Song; Lei Jiang; Yue Li; Yongsi Wang; Ning Chen; Peng Jiang; Sijia Zheng; Changchun Song; Xiaofeng Xu; Fenghui Yuan; Li Sun (CATENA, 2025)

Correction: Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Acute systemic inflammation induces region-specific morphological remodeling of astrocytes and microglia concurrent with depression-like behavior - An-Qi Zhang; Meng-Meng Zhang; Ling-Jie Li; Mei-Xue Yuan; Rong-Yu Liu; Peng Chen; Chen-Wei Wang; Yu Wang; Jiang-Ning Zhou; Qing-Hong Shan; Xin-Ya Qin (Histochemistry and Cell Biology, 2025)

LETM2 regulates mitochondrial function and autophagy in diabetic foot ulcers: implications for oxidative stress and therapeutic targeting - Nan Su; Jiwei Wang; Zhiwei Xue; Shujie Peng; Wenchen Xing; Haoyong Jin; Jiangli Zhao; Yanya He; Jiaqi Shi; Wenbo Li; Qijian Wei; Bin Huang; et al. (Functional & Integrative Genomics, 2025)

A CSDG photoelectronic transistor based on simulation model mimicking dopamine-facilitated synaptic plasticity for high energy-efficient neuromorphic system - Qing-an Ding; Yuhua Gao; Chunyan Liu; Chaoran Gu; Xiaoyuan Li; Fangfang Ning; Binghui Hou; Yandong Peng; Bing Chen (Cognitive Neurodynamics, 2025)

Probiotic characteristics and protective effects of chicken-derived Enterococcus faecium against infection with Avian Pathogenic Escherichia coli and Salmonella in laying hens - Yanan Cui; Kangping Liu; Peng Chen; Pengxin Jiang; Xutao Wang; Ning Chen; Jiamei Cui; Zijuan Hou; Puyu Liu; Jianguo Li; Shishan Dong; Qian Li; et al. (Veterinary Microbiology, 2025)

A novel mycotoxin-degrading enzyme complex can biodegrade AFB1, DON, and ZEN co-contamination in both in vitro and in vivo experiments - Yan-Qi Ning; Zhe Peng; Yu Zhang; Alainaa Refaie; Jing-Hui Ge; Li-Jia Guo; Wen-Jie Yang; Lv-Hui Sun (Toxicon, 2025)

A MAP (Monitoring–Assessment–Priority) framework for amine degradation products in carbon capture - Peng Chen; Xiao Li; Ningtong Yi; Xining (Ning) Wang; Shengtao Ma; Yali Yang; Xian Zhou; Yongqiang Ren; Shisen Xu; Xinghua Li (Journal of Hazardous Materials, 2025)

Residue carbon and C-degradation gene indicated the increase of soil organic carbon following vegetation restoration on the Loess Plateau, China - Rong Wang; Shicai Li; Yixian Ruan; Runhao Shi; Hongjian Hao; Yujie Liang; Ahejiang Sailike; Zhouchang Yu; Rong Fu; Ning Peng; Xinhui Han; Wei Zhang; et al. (Journal of Environmental Management, 2025)

Characterizations of air pollutants at roadside monitoring stations and traffic emission effects: A case study in Tianjin, China - Fangyuan Zheng; Junxia Gao; Lin Wu; Naixiu Sun; Wentian Xu; Qijun Zhang; Hongjun Mao; Jianfei Peng; Liwei Li; Ning Yang; Bin Liu (Journal of Environmental Sciences, 2025)

Spatio-temporal prevalence and distribution of Salmonella spp. serovars in animal-origin foods in China: A comprehensive outlook derived from nine years of national surveillance, 2014—2022 - Ying Li; Lisha Liu; Li Bai; Zhaoping Liu; Ning Li; Weijun Kang; Dajin Yang; Zixin Peng; Lingmei Niu (Food Research International, 2025)

Investigation of the matrix effects on structural stability and application performance of aptamers: Insights from tetrodotoxin detection in typical seafood - Yu Li; Shuo Qi; Peifang Chen; Mingwei Qin; Ning Ding; Chifang Peng; Zhouping Wang (Food Chemistry, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Formation mechanism and evolution characteristics of the loess–mudstone interface landslide in Yan’an, China - Penghui Ma; Qixian Jiao; Yalin Nan; Chuanzhi Zhang; Zekun Li; Luqing Zhao; Lisen Chen; Ning Han; Jianbing Peng (Bulletin of Engineering Geology and the Environment, 2025)

Resveratrol improves boar semen quality in summer months through modulation of the AGEs-RAGE signaling pathway in Leydig cells - Zhiyun Peng; Zereng Chen; Xiaofang Lu; Li Zhang; Ning Gao; Bo Weng; Tuo Xu; Heng Bao; Maoliang Ran (Journal of Thermal Biology, 2025)

Electrochemical membrane bioreactors for wastewater treatment: Mechanisms of membrane fouling control and applications to refractory pollutants - Shuli Liu; Yatong Gao; Xiaohong Han; Jiajun Hua; Yuhong Zhang; Glen T. Daigger; Qi Li; Ning Guo; Xiao Mi; Jia Kang; Peng Zhang (Journal of Environmental Chemical Engineering, 2025)

Evolution of loess gullies and geohazard chains in the Dongzhi tableland, China - Penghui Ma; Ning Han; Qiangbing Huang; Yanbo Cao; Zekun Li; Lisen Chen; Qixian Jiao; Jianbing Peng (Geomorphology, 2025)

Unveiling the intrinsic electrochemical properties and stability of phase-pure A5B19 La–Mg–Ni-based superlattice allotropes - Kuiyue Wang; Anyi Zhang; Ning Zhang; Wenfeng Wang; Shumin Han; Qiuming Peng; Yuan Li; Lu Zhang (Chemical Engineering Journal, 2025)

Polymer bidirectional induction for ultrathin ZIF-8 membrane with chemisorption site towards in-situ enhanced H2/CO2 separation - Peng Li; Chao Ma; Ning Li; Chi Tang; Zhaolin Lv; Zhenjie Gu; Zhihua Qiao; Chongli Zhong (Chemical Engineering Journal, 2025)

Poly-γ-glutamic acid could enhance the salt resistance of maize by collectively increasing the osmotic, ion, and oxidative stresses resistance and enriching the salt-tolerant PGPBs in rhizosphere soil - Haizhen Ma; Ning Xiao; Yifan Liu; Jiang Liu; Peng Li; Xinru Deng; Jia Wei; Panpan Li; Tao Xia (Plant and Soil, 2025)

Revealing the occurrence characteristics, interaction mechanisms, and health risk of phthalates in agricultural soil of arid regions across Northwest China - Guo-dong Kang; Peng Lei; Lei-lei Lu; Ning Wang; Meng-jiao Li; Liang-liang Liu; Rui-yun Sun; Sheng-hu Zhang; Yan-hua Liu; Ping Wu (Environmental Monitoring and Assessment, 2025)

YOLO-feed: An advanced lightweight network enabling real-time, high-precision detection of feed pellets on CPU devices and its applications in quantifying individual fish feed intake - Miaosheng Feng; Pengxin Jiang; Yuhang Wang; Shuimu Hu; Sijing Chen; Rui Li; Haibin Huang; Ning Li; Boyu Zhang; Qiaozhen Ke; Yu Zhang; Peng Xu (Aquaculture, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Heave motion estimation based on the Cubature Kalman Filter combined with Fast Fourier Transform of acceleration autocorrelation - Daoxi Li; Shuqing Wang; Donghong Ning; Jiajing Peng (Ocean Engineering, 2025)

OsATG1 and OsATG8 exhibit autophagy-independent functions to oppositely regulate ROP GTPase-mediated plant immunity in rice - Feng He; Hui Tao; Ruyi Wang; Jinling Liu; Zeyun Hao; Debao Wang; Xuetao Shi; Fan Zhang; Jiawei Long; Hao Zhang; Xiao Yang; Mengchao Qin; et al. (Molecular Plant, 2025)

The effect of inclined plate motion on the classification efficiency of quartz sand in the Reflux Classifier - Zhiyuan Zhang; Dongjiao Gui; Peng Chen; Yifei Li; Ning Han; Yanfeng Li (Minerals Engineering, 2025)

Selenium-enriched lactic acid bacteria inoculation enhances the quality of Paocai by imparting the microbiome and metabolome - Mingye Peng; Qin Li; Binbin Long; Bo Li; Zhicong Shen; Ning Xu; Yong Hu; Chao Wang; Yang Chen; Mengzhou Zhou (Food Chemistry, 2025)

Associations of phthalate metabolites in urine and follicular fluid with endometrial thickness in the TREE cohort - Xiu-Ting Li; Chong Liu; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; A.-Xue Liu; Yang-Juan Li; Jin-Qin Zhu; Ning Zhang; Juan Li; et al. (Environmental Toxicology and Pharmacology, 2025)

Dielectrically optimized Ni/CeO2/CNT catalysts for low-power and stable microwave-assisted dry reforming of methane - Tingting Wang; Xiaojun Li; Fengjuan Liu; Bei Liu; Xinkang Peng; Zhiheng Wang; Ning Qu; Jie Kong; Zhenchen Tang; Feng Zeng; Han Lin; Xiaohua Lu; et al. (Chemical Engineering Journal, 2025)

Reactive species-mediated biodegradability improvement of biogas slurry in a Fenton-like system - Xianglin Chang; Haoxi Dai; Lan Liang; Wenchao Peng; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Ning Li (Chemical Engineering Journal, 2025)

Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Physiological and transcriptomic responses of fall armyworm, Spodoptera frugiperda to host-plant switching - Jun Peng; Renwen Zheng; Jinyuan Zhao; Jinhui Zhang; Qianqian Li; Dongyan Huang; Xin Zhou; Lijuan Liu; Zhuocong Li; Xiaoman Ning; Sihan Lu; Qingfeng Tang (Journal of Pest Science, 2025)

MTGGF: A Metabolism Type-Aware Graph Generative Model for Molecular Metabolite Prediction - Peng-Cheng Zhao; Xue-Xin Wei; Qiong Wang; Hao-Yang Wang; Bing-Xue Du; Jia-Ning Li; Bei Zhu; Hui Yu; Jian-Yu Shi (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Genomic Approaches to Enhance Disease Resistance in Large Yellow Croaker: Recent Progress and Future Perspectives - Zhou Jiang; Yulin Bai; Ning Li; Lin Chen; Ji Zhao; Yin Li; Tao Zhou; Peng Xu (Reviews in Aquaculture, 2025)
Large yellow croaker is an important marine aquaculture species in China, but frequent disease outbreaks have led to significant losses in the aquaculture industry. Although traditional genetic selection methods have long been applied in fish breeding, an increasing number of studies are introducing genomic selection methods into large yellow croaker breeding to target complex traits such as disease resistance. Recent advancements in genomic resources, including an updated reference genome and SNP array, have opened up new opportunities for genetic and evolutionary research on this species. This review provides an overview of the current status of the large yellow croaker aquaculture industry and the existing approaches to addressing disease challenges. It also summarizes genomic selection techniques, the genetic mechanisms underlying disease resistance traits, and potential improvements in genomic selection methods. Furthermore, we summarize future directions for large yellow croaker breeding, incorporating the application of genetic research, multi‐dimensional data integration, standardized testing protocols, and artificial intelligence for phenotypic measurement. These strategies have opened new pathways to enhance disease resistance in large yellow croaker and to promote the sustainable development of its aquaculture industry.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Annual growth bands in the late Carboniferous reef-building colonial rugose coral Ivanovia and their environmental significance - Yong-Li Zhang; Wen-Tao Huang; En-Pu Gong; Guan-Ming Lai; Mark A. Wilson; Jun-Jie Wang; Ning-Feng Du; De-Peng Li (Palaeoworld, 2025)

Long-range electron transfer pathways at FeCu bimetallic interfaces: Bridging catalytic mechanisms and scalable applications for persistent pollutant degradation - Xiaoyin You; Chaohai Wang; Chuqiao Wang; Xing Xu; Yuying Hu; Ning Li; Fengping Hu; Wen Liu; Xiaoming Peng (Journal of Hazardous Materials, 2025)

Detecting Deleterious Recessive Variants in Large Yellow Croaker Using Data from 7337 Individuals - Zhou Jiang; Ji Zhao; Ning Li; Jiaying Wang; Fei Pu; Hongshu Chi; Peng Xu; Tao Zhou (Marine Biotechnology, 2025)

Neonicotinoid pesticides: residue detection and dietary risk assessment in commercially available plant-based agricultural products in North China - Peng Sun; Danqi Ren; Guotao Ding; Ning Hao; Ge Shi; Weihao Li (Environmental Monitoring and Assessment, 2025)

Two new megastigmane glycosides from the leaves of Nicotiana tabacum and their anti-inflammatory activities - Peng-fei Yang; Wei Wu; Hang-hang Han; Qing-fu Wang; Lei Li; Ze-ning Wang; Duo-bin Mao; Zhi-fei Chen (Natural Product Research, 2025)

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

Sesquiterpenoids isolated from the root bark of Lycium chinense - Xiao-xia Wang; Qian Liu; Ning Wang; Rui-li Zhang; Xiao Li; Peng-yu Zhuang; Hang Liu; Liang-dan Sun; Yang Jin (Phytochemistry, 2025)

Emerging MXene-based catalysts for advanced oxidation processes - Yanlei Zhu; Ning Li; Rui Wang; Longfei Zhang; Yong Liu; Wenchao Peng; Jiapeng Liu (Fuel, 2025)

Tiller growth and mortality in winter wheat as affected by carbon and nitrogen partitioning via stem internode structure - Xiaojie Feng; Lu Yang; Suoqian Kang; Yangbo Huai; Yuanwei Gan; Shuhui Song; Yonghua Li; Peng Ning (Field Crops Research, 2025)

Cascade-responsive nanoplatform for synergistic cancer therapy via ROS amplification and hypoxia targeting - Chunyun Xu; Yanfang Ding; Jingjing Qi; Peng Chu; Hongjie Huo; Zhuang Wang; Qingxuan Han; Yuan Liang; Ning Yang; Youwei Xu; Ligeng Xu; Lixue Chen; et al. (Chemical Engineering Journal, 2025)

Mxene quantum dot insertion-induced electron transfer in CoFe LDH for high-performance zinc-air batteries - Qing Sun; Kailin Li; Tie Shu; Ziyang Guo; Yongfei Li; Yuxin Zhang; Liang Li; Jiaoyi Ning; Peng Zhao; Ke Xin Yao (Chemical Engineering Journal, 2025)

The failure modes and evolution process of loess landslide dams via flume tests - Zekun Li; Penghui Ma; Ning Han; Qixian Jiao; Lisen Chen; Lin Ran; Zhijie Jia; Luqing Zhao; Jingjing Nan; Jianbing Peng (Landslides, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Localized chemical disorder induced superior energy storage performance of PbZrO3-based antiferroelectric ceramics - Mingqi Shi; Xingke Pan; Dingheng Lin; Ning Liu; Wei Zhang; Sen Chen; Peng Li; Jinjun Liu; Hongzhen Xie; Zhongbin Pan (Chemical Engineering Journal, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Upper limit of ice content at the lunar south pole as revealed by the Earth-based SYISR–FAST bistatic radar system - Mingyuan Li; Jinghai Sun; Xin’an Yue; Honglei Lin; Zhiqing Chen; Feng Ding; Baiqi Ning; Yong Wei; Chi Wang; Peng Jiang (Science Bulletin, 2025)

Study on the Flow Velocity Preference of the Four Major Chinese Carps Using Convolutional Neural Networks - Ning Qiu; Wenjing Li; Yi Yu; Jianna Jia; Guoqiang Ma; Shitao Peng (Fishes, 2025)
Flow velocity is a critical factor in determining the suitability of fish habitats. Understanding the preference patterns of the four major Chinese carps (FMCCs) for different flow velocities is crucial for their habitat conservation and restoration. In this study, the preference of individual fish species, approximately 15 cm in length, for flow velocity was investigated at flow velocity gradients of 0.0, 0.4, 0.8, 1.2, 1.6, and 2.0 times their body length. Additionally, a deep learning algorithm based on convolutional neural networks (CNNs) was employed for fish target detection. The results showed that, at this length, black carp (Mylopharyngodon piceus) preferred fast currents when the inlet flow velocity was between 0.4 and 1.6 times their body length, while grass carp (Ctenopharyngodon idella), silver carp (Hypophthalmichthys molitrix), and bighead carp (Hypophthalmichthys nobilis) preferred fast currents when the inlet flow velocity of the test flume was between 0.4 and 2.0 times their body length. However, this preference for fast currents decreased as the overall flow velocity increased to a specific threshold, eventually leading to their avoidance. The highest preference for fast currents among the four species was observed at inlet flow velocities of 1.2, 0.4, 0.8, and 0.8 times their body length, respectively. The findings of this study provide important insights into habitat conservation and restoration for the FMCCs in projects focused on the construction of navigation channels and water conservancy.

Construct favorable solid electrolyte interphase by applying alternating current discharge during battery formation - Yulong Zhang; Shiyou Li; Meiling Wu; Lijuan Wang; Ning He; Yin Quan; Peng Wang; Dongni Zhao; Xiaoling Cui (Chemical Engineering Journal, 2025)

Ruthenium-doped carbon dots with “three-in-one” chemodynamic, photodynamic, and photothermal activity induce panoptosis for tumor therapy - Xiaokang Lu; Weijie Sun; Xingye Zheng; Lishen Yang; Tan Feng; Xiaoqin Deng; Fengqi Zhou; Hongmin Zhu; Ding Ma; Bilian Li; Guobao Ning; Hang Chen; et al. (Chemical Engineering Journal, 2025)

Knowledge of microalgal Rubiscos helps to improve photosynthetic efficiency of crops - Tongtong Zhu; Peng Ning; Yiguo Liu; Min Liu; Jianming Yang; Zhaobao Wang; Meijie Li (Planta, 2025)

Histaminergic Innervation of the Ventral Anterior Thalamic Nucleus Alleviates Motor Deficits in a 6-OHDA-Induced Rat Model of Parkinson’s Disease - Han-Ting Xu; Xiao-Ya Xi; Shuang Zhou; Yun-Yong Xie; Zhi-San Cui; Bei-Bei Zhang; Shu-Tao Xie; Hong-Zhao Li; Qi-Peng Zhang; Yang Pan; Xiao-Yang Zhang; Jing-Ning Zhu (Neuroscience Bulletin, 2025)
The ventral anterior (VA) nucleus of the thalamus is a major target of the basal ganglia and is closely associated with the pathogenesis of Parkinson’s disease (PD). Notably, the VA receives direct innervation from the hypothalamic histaminergic system. However, its role in PD remains unknown. Here, we assessed the contribution of histamine to VA neuronal activity and PD motor deficits. Functional magnetic resonance imaging showed reduced VA activity in PD patients. Optogenetic activation of VA neurons or histaminergic afferents significantly alleviated motor deficits in 6-OHDA-induced PD rats. Furthermore, histamine excited VA neurons via H1 and H2 receptors and their coupled hyperpolarization-activated cyclic nucleotide-gated channels, inward-rectifier K + channels, or Ca 2+ -activated K + channels. These results demonstrate that histaminergic afferents actively compensate for Parkinsonian motor deficits by biasing VA activity. These findings suggest that targeting VA histamine receptors and downstream ion channels may be a potential therapeutic strategy for PD motor dysfunction.

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Mink enteritis virus infection induced cell cycle arrest and autophagy for its replication - Dong Lu-jiao; Li Zhi-juan; Sun Ying-Li; Fan Hua; Li Wen-qian; Zhang Hui-ning; Peng Jun; Xie Zhi-jing (Veterinary Microbiology, 2025)

Spatio-temporal characteristics and influencing factors of water quality in Xiangxi Bay under the operation of the three gorges reservoir - Aiping Jiang; Dongsheng Wang; Zhen Ning; Peng Li; Tao Xu; Boran Zhu; Qidong Peng; Tiantian Jin; Junqiang Lin; Di Zhang (Journal of Contaminant Hydrology, 2025)

Immune regulation differences in Large yellow croaker with varied resistance to Cryptocaryon irritans infection - Zhou Jiang; Ji Zhao; Rui Li; Qiaozhen Ke; Jiaying Wang; Yin Li; Shuimu Hu; Junjia Zeng; Fei Pu; Ning Li; Peng Xu; Tao Zhou (Fish & Shellfish Immunology, 2025)

Noncovalently functionalized carbon microspheres for separating no-carrier added 177Lu from real neutron-irradiated 176Yb target - Guoquan Ma; Haiyue Peng; Xisheng Fan; Yuqi Guo; Yang Li; Jing Gao; Yingjiang Hu; Bo Li; Yuanyou Yang; Jingsong Zhang; Lijian Ma; Ning Liu; et al. (Chemical Engineering Journal, 2025)

Susceptibility of Soil Elements to Biotic and Abiotic Factors in a Forest-Steppe Ecotone - Qiuhua Li; Jiayun Zhang; Chunbo Li; Hong Ji; Xiaomeng Ma; Peng He; Lixin Yu; Mengfan Zhou; Ning Dang; Jishuai Su; Ruzhen Wang; Heyong Liu; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Molecular evidence for goose astrovirus 2 and goose astrovirus 3 coinfection in goslings with gout - Chen Guo; Jingjing Huang; Xiaoyang Hu; Qiong Li; Yinuo Song; Duo Peng; Kang Ning; Xiaoyan Wang; Dabing Zhang (Archives of Virology, 2025)

Design and Testing of an autonomous laser weeding robot for strawberry fields based on DIN-LW-YOLO - Peng Zhao; Junlin Chen; Jiahao Li; Jifeng Ning; Yongming Chang; Shuqin Yang (Computers and Electronics in Agriculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Cu/TiO2 adsorbents modified by air plasma for adsorption–oxidation of H2S - Yongqi Yan; Xinyu Yang; Ping Ning; Chi Wang; Xin Sun; Fei Wang; Peng Gao; Kai Li (Journal of Environmental Sciences, 2025)

Different contributions of microbial and plant residues to soil organic carbon accumulation during planted forest and abandoned farmland restoration, Loess Plateau, China - Hongjian Hao; Rong Wang; Shicai Li; Duo Pian; Ning Peng; Ahejiang Sailike; Zhouchang Yu; Jiayi Shi; Xingbo Wang; Zihan Wang; Wei Zhang (Plant and Soil, 2025)

Knowledge-based phosphorus input levels control the link between soil microbial diversity and ecosystem functions in paddy fields - Qiaorong Li; Yao Liu; Ning Su; Chang Tian; Yuping Zhang; Lin Tan; Jianwei Peng; Xiangmin Rong; Gongwen Luo (Agriculture, Ecosystems & Environment, 2025)

Soil labile organic carbon and nitrate nitrogen are the main factors driving carbon-fixing pathways during vegetation restoration in the Loess Plateau, China - Yujie Liang; Rong Fu; Ahejiang Sailike; Hongjian Hao; Zhouchang Yu; Rong Wang; Ning Peng; Shicai Li; Wei Zhang; Yangyang Liu (Agriculture, Ecosystems & Environment, 2025)

200 years of Portland cement: Technological advancements and sustainability challenges - Hao Chen; Ning Li; Cise Unluer; Peng Chen; Zuhua Zhang (Journal of Cleaner Production, 2025)

Probe on the pivotal role of green rust in improving the enzymatic activity and facilitating the formation of 1O2 in Fenton-like process for degradation of 4-chlorophenol - Jie Peng; Meng Li; Qian Zhang; Zefeng Li; Ziqi Zhao; Yuwei Ding; Ning Du (Journal of Environmental Management, 2025)

Investigating the interaction mechanisms between arachin and resveratrol: Utilizing multi-spectroscopy and computational chemistry - Yu-qi Yang; Qi Gao; Shi-qi Yue; Xue Peng; Ning Wang; Jing-li Xin; Miao Yu; Jia-jia Rao; You-lin Xue (Food Chemistry, 2025)

Multi-period optimal scheduling of building loads based on accurate virtual battery model - Xiuli Zhu; Peng Wang; Ning Li; Weiwu Yan (Energy and Buildings, 2025)

Enhancing fire suppression in restricted spaces with fine water mist microcapsules - Yijun Ren; Peng Zhang; Hairui Bian; Dang Ding; Chen Li; Ning Sang; Jiachao Zhang; Fangsheng Huang; Zhiqiang Zhu (Chemical Engineering Journal, 2025)

Activation potential decreasing of iron oxide/graphite felt cathode by introducing Mn in electrochemical Fenton-like reactions - Yalong Xu; Weijian Li; Jun Wang; Di Wu; Ning Li; Yang Li; Xiaobin Fan; Wenchao Peng (Chemosphere, 2024)

Roadside measurement of N2O and CH4 emissions from vehicles in Hong Kong - Mengyuan Chu; Peter Brimblecombe; Nirmal Kumar Gali; Meisam Ahmadi Ghadikolaei; Peng Wei; Xin Li; Shiyi Yang; Yuanhui Wei; Zhi Ning (Science of The Total Environment, 2024)

Chiral FeNC single-atom nanozymes with multi-enzyme activity for dye degradation - Guobao Ning; Huan Liang; Linjiang Guo; Xiaokang Lu; Lin Xiao; Tianle Qi; Hui Zhao; Can-Peng Li (Journal of Environmental Chemical Engineering, 2024)

Cation exchange strategy of ellagic acid-based microporous metal-organic framework for efficient CO2/N2 and CO2/CH4 separation - Chen-Ning Li; Zhi-Peng Tao; Lin Liu; Daqiang Yuan; Zheng-Bo Han (Chemical Engineering Journal, 2024)

Enhanced Adsorption of Cadmium onto Microplastics Derived from Polyethylene Mulching Film by Weathering - Lu Wang; Ruichang Zhang; Shufa Zhu; Jing Li; Xinquan Zhou; Ning Zhang; Shuge Peng; Xuefeng Wei (Water, Air, & Soil Pollution, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Green synthesis of diatom–allophane bio-nanocomposites for highly efficient oxytetracycline adsorption - Mengyuan Li; Shun Wang; Dong Liu; Dusan Losic; Ning Zhao; Qian Tian; Yuguo Shen; Rongda Yu; Hao Liu; Qiyi Ma; Peng Yuan (Science of The Total Environment, 2024)

Reproductive resilience of growth and nitrogen uptake underpins yield improvement in winter wheat with forced delay of sowing - Xiaojie Feng; Yangbo Huai; Suoqian Kang; Lu Yang; Yonghua Li; Jiaru Feng; Zhe Zhang; Michael J.W. Maw; Zhenling Cui; Peng Ning (Science of The Total Environment, 2024)

Physicochemical properties, structural characteristics and protein digestibility of pea protein-wheat gluten composited meat analogues prepared via high-moisture extrusion - Yu-Ru Zhao; Ning Peng; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Cai-Yue Wang; Zi-Yue Wang; Chenying Wang; Xidong Ren (Food Hydrocolloids, 2024)

Three birds with one stone: A nano zeolitic imidazolate framework-luciferase-antimicrobial peptide biocomposite-based biosensing platform for improving enzyme stability, detection sensitivity, and sterilization effect - Renjie Zhou; Tingting He; Linhao Peng; Dengfeng Li; Zhenzhong Yu; Xin Yang; Ning Gan (Chemical Engineering Journal, 2024)

A fire risk pre-warning framework for high-rise buildings based on unascertained method - Li-Ning Zhang; Xiang-Ming Wang; Jing An; Hong Xian Li; Jiao-Qian Guo; Guo-bo Han; Peng-Fei Gou (Environmental Science and Pollution Research, 2024)
The growing global interest in preventing and controlling fires in high-rise buildings reflects the increasing significance of this issue today. This research aims to establish an early warning framework for fire risk in high-rise buildings. Firstly, considering the importance of a scientific indicator system for the application of the model, this study combines the event analysis method with the building design fire code to identify 11 key risk factors that have a far-reaching impact on the prevention of fires in high-rise buildings. Based on identifying the risk factors, a high-rise building fire risk warning tree is also established, which scientifically solves the problem of the indicator system of the warning object. Subsequently, in response to the various complex issues arising from the uncertainty of fire occurrence in high-rise buildings, this study adopts the unascertained method to model the fire risk of high-rise buildings for early warning. In addition, the developed methodology was empirically validated through case studies and analyses of empirical data on fire risks in nine representative high-rise buildings. The results of the unascertained method were also compared with the results of the K-means method, from which it was concluded that the unascertained method can predict building fires more accurately. The research results provide a reliable decision support system for fire disaster prevention and control in high-rise buildings.

Relevance of genetic causes and environmental adaptation of Cronobacter spp. isolated from infant and follow-up formula production factories and retailed products in China: A 7-year period of continuous surveillance based on genome-wide analysis - Wei Tong; Dajin Yang; Shaofu Qiu; Sai Tian; Zehong Ye; Shuran Yang; Lin Yan; Weiwei Li; Ning Li; Xiaoyan Pei; Zhongqing Sun; Chengwei Liu; et al. (Science of The Total Environment, 2024)

Molecular weight-dependent differences in spectral properties and metal-binding behaviors of dissolved organic matter from different lakes - Keli Yang; Yaoling Zhang; Jiaoyu Peng; Huacheng Xu; Xin Liu; Haining Liu; Ning Li; Laodong Guo; Wu Li (Science of The Total Environment, 2024)

High sulfur-to-iron ratios enhance thallium(I) sequestration by sulfidated zero-valent iron - Nana Wang; Fengli Liu; Huosheng Li; Ping Zhang; Juanxi Huang; Gaosheng Zhang; Tangfu Xiao; Jianyou Long; Dan Peng; Yuqi Wang; Huanbin Huang; Zengping Ning (Process Safety and Environmental Protection, 2024)

High efficiency separation of bastnaesite (REFCO3) and monazite (REPO4) in mixed rare earth concentrate by heating under N2 and leaching with HCl/AlCl3 - Jiahao He; Peng Gao; Shuai Yuan; Shaokai Cheng; Jilai Ning; Zhenya Zhou; Yongsheng Sun; Wenbo Li (Hydrometallurgy, 2024)

A reliable fluorescence “turn-on” aptasensor based on dual-emitting europium metal-organic frameworks for ultrasensitive and selective detection of sulfamethazine - Qingxiang Liu; Xuelian Hu; Xiaoxiao Dong; Peng Liu; Ning Zhang; Zhe Gao; Wenxiu Wang; Huiling Li; Shuo Wang; Xiuying Liu; Yiwei Tang (Food Chemistry, 2024)

Surface phosphorylated Li5FeO4 prelithiation additive synergistically improves the air-stability and lithium-ion conductivity - Lei Niu; Meiling Wu; Yulong Zhang; Cankun Gao; Xin Li; Hao Ding; Ning He; Peng Wang; Jiawen Zhang; Jingxuan Yan; Ningshuang Zhang; Dongni Zhao; et al. (Chemical Engineering Journal, 2024)

Rechargeable Self-Powered pressure sensor based on Zn-ion battery with high sensitivity and Broad-Range response - Yong-Peng Hu; Kai-Yang Liu; Ruo-Ning Bai; Da-Zhuang Liu; Wei Yu; Chui-Zhou Meng; Guo-Xian Li; Shi-Jie Guo (Chemical Engineering Journal, 2024)

Short-length SSVEP data extension by a novel generative adversarial networks based framework - Yudong Pan; Ning Li; Yangsong Zhang; Peng Xu; Dezhong Yao (Cognitive Neurodynamics, 2024)

Meta-omics analysis reveals the marine arsenic cycle driven by bacteria - Zhao-Jie Teng; Jian Li; Peng Wang; Chun-Yang Li; Ming Peng; Qi-Long Qin; Xiu-Lan Chen; Yin Chen; Hui-Hui Fu; Ning Wang; Yu-Zhong Zhang (Journal of Hazardous Materials, 2024)

Investigating the impact of ultrasound on the structural, physicochemical, and emulsifying characteristics of Dioscorin: Insights from experimental data and molecular dynamics simulation - Qi Gao; Yu-qi Yang; Hao-nan Nie; Bing-qing Wang; Xue Peng; Ning Wang; Jiang-kuo Li; Jia-jia Rao; You-lin Xue (Food Chemistry, 2024)

SS-31 mitigates oxidative stress and restores mitochondrial function in cigarette smoke-damaged oral epithelial cells via PINK1-mediated mitophagy - Pei Ye; Hong Liu; Yao Qin; Zhiyuan Li; Zhuwei Huang; Xiangwen Bu; Qiao Peng; Ning Duan; Wenmei Wang; Xiang Wang (Chemico-Biological Interactions, 2024)

Accelerated screening of active sites on biochar for catalysis and adsorption via multidimensional fingerprint factor descriptors - Wenjie Gao; Ning Li; Zhanjun Cheng; Beibei Yan; Wenchao Peng; Shaobin Wang; Guanyi Chen (Bioresource Technology, 2024)

The Carbon and Nitrogen Balance in Developing Grains Affects Grain Protein Concentrations in Two Wheat Varieties with Similar Yields - Xiaojie Feng; Yonghua Li; Suoqian Kang; Yangbo Huai; Fengmei Zhang; Peng Ning (International Journal of Plant Production, 2024)

Evaluation of a new real-time source apportionment system of PM2.5 and its implication on rapid aging of vehicle exhaust - Pei-Ting Yao; Xing Peng; Li-Ming Cao; Li-Wu Zeng; Ning Feng; Ling-Yan He; Xiao-Feng Huang (Science of The Total Environment, 2024)

Organic radicals driving polycyclic aromatic hydrocarbon polymerization with peracetic acid activation in soil - Ziyue Li; Xiaolei Wang; Fei Peng; Ning Chen; Guodong Fang (Journal of Hazardous Materials, 2024)

Loss of microbial functional diversity following Spartina alterniflora invasion reduces the potential of carbon sequestration and nitrogen removal in mangrove sediments—from a gene perspective - Zetao Dai; Ning Zhang; Feifei Wang; Yujie Li; Jiarui Peng; Tao Xiang; Xiaoyu Zhao; Shengchang Yang; Wenzhi Cao (Journal of Environmental Management, 2024)

Soil improvement using biostimulated MICP: Mechanical and biochemical experiments, reactive transport modelling, and parametric analysis - Yi-jie Wang; Wen-bo Chen; Peng-lin Li; Zhen-yu Yin; Jian-hua Yin; Ning-jun Jiang (Computers and Geotechnics, 2024)

Modulating proportion of Ni0 species stabilized by Ni2+ on Ni-MgO catalyst with superior stability for dry reforming of methane - Xieyi Liu; Junjie Wen; Yu xie; Zongling Li; Manshu Zhong; Rongbing Nie; Shiyuan Peng; Jinyan Cao; Jianjun Chen; Ping Ning; Qiulin Zhang (Chemical Engineering Journal, 2024)

A blue light 3D printable hydrogel with water absorption, antibacterial, and hemostatic properties for skin wound healing - Xiu-Chong He; Xiu-Ning Chen; Yi-Hao Liu; Xinyu Zhong; Lei Qiang; Hong-Qin Wang; Fang-Zhou Wang; Jun-Song Wang; Cheng-Hui Li; Peng-Fei Zheng (Chemical Engineering Journal, 2024)

Alternating wet and dry irrigation cycles enhance the nitrogen “cache” function of duckweed in a rice-duckweed system - Weixuan Liu; Junzeng Xu; Yawei Li; Xiaoyin Liu; Ning Gao; Zeeshan Ahmed; Yihao Peng; Hao Liang; Qianjing Jiang; Yong He (Agriculture, Ecosystems & Environment, 2024)

Application of airborne gamma-ray spectrometry in geological lithology mapping—a case study of a region in the Qinling Mountains, China - Yongzai Xi; Guixiang Liao; Yongbo Li; Junjie Liu; Shan Wu; Ning Lu; Peng He (Acta Geophysica, 2024)

An Algorithm for Ship Detection in Complex Observation Scenarios Based on Mooring Buoys - Wenbo Li; Chunlin Ning; Yue Fang; Guozheng Yuan; Peng Zhou; Chao Li (Journal of Marine Science and Engineering, 2024)
Marine anchor buoys, as fixed-point profile observation platforms, are highly susceptible to the threat of ship collisions. Installing cameras on buoys can effectively monitor and collect evidence from ships. However, when using a camera to capture images, it is often affected by the continuous shaking of buoys and rainy and foggy weather, resulting in problems such as blurred images and rain and fog occlusion. To address these problems, this paper proposes an improved YOLOv8 algorithm. Firstly, the polarized self-attention (PSA) mechanism is introduced to preserve the high-resolution features of the original deep convolutional neural network and solve the problem of image spatial resolution degradation caused by shaking. Secondly, by introducing the multi-head self-attention (MHSA) mechanism in the neck network, the interference of rain and fog background is weakened, and the feature fusion ability of the network is improved. Finally, in the head network, this model combines additional small object detection heads to improve the accuracy of small object detection. Additionally, to enhance the algorithm’s adaptability to camera detection scenarios, this paper simulates scenarios, including shaking blur, rain, and foggy conditions. In the end, numerous comparative experiments on a self-made dataset show that the algorithm proposed in this study achieved 94.2% mAP50 and 73.2% mAP50:95 in various complex environments, which is superior to other advanced object detection algorithms.

SIRT6 positively regulates antiviral response in a bony fish, the Chinese perch Siniperca chuatsi - Xiang Yang Wu; Zhi Wei Zhang; Shan Nan Chen; An Ning Pang; Xue Yun Peng; Nan Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2024)

Enhancing crop productivity and resilience by promoting soil organic carbon and moisture in wheat and maize rotation - Yonghua Li; Xiaojie Feng; Yangbo Huai; Mahmood UI Hassan; Zhenling Cui; Peng Ning (Agriculture, Ecosystems & Environment, 2024)

Genomic analysis of Cobetia sp. D5 reveals its role in marine sulfur cycling - Xiao-Mei Geng; Shi-Ning Cai; Hai-Xia Zhu; Zhi-Gang Tang; Chun-Yang Li; Hui-Hui Fu; Yi Zhang; Hai-Yan Cao; Peng Wang; Mei-Ling Sun (Marine Genomics, 2024)

Antimicrobial susceptibility and genomic characterization of Vibrio parahaemolyticus isolated from aquatic foods in 15 provinces, China, 2020 - Yao Bai; Qiuping Yang; Yanan Sun; Fengqin Li; Jiali Sun; Shuran Yang; Dajin Yang; Zixin Peng; Baowei Yang; Jin Xu; Yinping Dong; Shaofei Yan; et al. (International Journal of Food Microbiology, 2024)

Effect of sludge redistribution strategy on stability of partial nitrification-anammox process: Further exploration of the potential value of sludge - Peng Wang; Rui Ou; Jun Tan; Ning Li; Min Zheng; Qinghai Jin; Jin Yu; Di He (Chemosphere, 2024)

Associations of ambient ozone exposure and CD4+ T cell levels with mortality among people living with HIV: An eight-year longitudinal study - Hao Chen; Kai Zhang; Dongying Wei; Jiawen Zhu; Weiyi Tian; Jinli Mo; Hongbin Peng; Xia Luo; Yinxia Liang; Yanna Pan; Li Jiang; Yunan Xu; et al. (Science of The Total Environment, 2024)

Antimony and arsenic migration in a heterogeneous subsurface at an abandoned antimony smelter under rainfall - Chao Li; Yiyuan Ran; Pan Wu; Peng Liu; Boyi Yang; Xueyuan Gu; Ping Zhao; Shirong Liu; Lei Song; Yuhui Liu; Yizhang Liu; Zengping Ning; et al. (Journal of Hazardous Materials, 2024)

Can the concentration of environmentally persistent free radicals describe its toxicity to Caenorhabditis elegans? Evidence provided by neurotoxicity and oxidative stress - Huijie Li; Hao Li; Ning Zuo; Di Lang; Wei Du; Peng Zhang; Bo Pan (Journal of Hazardous Materials, 2024)

Synthesis and Application of Specific N2H4 Fluorescent Probes with AIE Effect Based on Pyrazole Structure - Yun-Shang Yang; Zhen Zhang; Ying-Peng Zhang; Yu-Ning Liang; Xing-Xing Li; Zhi-Dong Teng (Journal of Fluorescence, 2024)

ALKBH5 SUMOylation-mediated FBXW7 m6A modification regulates alveolar cells senescence during 1-nitropyrene-induced pulmonary fibrosis - Se-Ruo Li; Ning-Ning Kang; Rong-Rong Wang; Meng-Die Li; Li-Hong Chen; Peng Zhou; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Electric-field-controlled energy barrier and reaction pathway ensure high sulfur product selectivity in Cu/γ-Al2O3 catalyst-assisted DBD plasma conversion of carbonyl sulfide - Yixing Ma; Peng Chen; Defu Li; Fei Wang; Langlang Wang; Kai Li; Ping Ning; Xueqian Wang; Kostya (Ken) Ostrikov (Journal of Environmental Chemical Engineering, 2024)

The removal mechanisms of HF and HCl gases using Mg-Al adsorbent prepared by sol-gel synthesis method - Peng Gao; Jiayu Feng; Yuxuan Xie; Xinyu Yang; Ping Ning; Xin Sun; Fei Wang; Lei Shi; Jie Zhao; Kai Li (Journal of Environmental Chemical Engineering, 2024)

Application of g-C3N4-based photocatalysts for N2 photofixation - Longjian Li; Ping Zhang; Ning Li; Tuerhong Reyila; Yongchong Yu; Xiaoping Su; Cheng Peng; Lijuan Han (Journal of Environmental Chemical Engineering, 2024)

Nitrogen-doped substrate material ion imprinting–capacitive deionization selective recovery of lithium ions from acidic solutions - Yifei Li; Ning Han; Qiongqiong He; Haisen Peng; Xiaoqi Wu; Zhen Meng; Zhenyong Miao (Environmental Science and Pollution Research, 2024)

Effects of the Glucocorticoid-Mediated Mitochondrial Translocation of Glucocorticoid Receptors on Oxidative Stress and Pyroptosis in BV-2 Microglia - Ruonan Dang; Xuyang Hou; Xinglan Huang; Caifeng Huang; Xiaoqing Zhao; Xingrong Wang; Ning Zhang; Yuqi Yang; Nan Li; Sheng Liu; Peng Yan; Ping Fan; et al. (Journal of Molecular Neuroscience, 2024)

Structural/surface characterization of transition metal element–doped H-ZSM-5 adsorbent for CH3SH removal: identification of active adsorption sites and deactivation mechanism - Yuxuan Xie; Xiao Peng; Xin Song; Ping Ning; Xin Sun; Yixing Ma; Chi Wang; Kai Li (Environmental Science and Pollution Research, 2024)

Performance assessment of solar photovoltaic-based constructed wetland for sustainable rural wastewater treatment - Ye Yang; Chao-Kun Li; Liu Han; Zhi-Peng Yang; Ning-Ning Xiao; Nan Zhang; Ying-Ying Dong; Zhi-Wen Chen; Hui Xi; Wen-Dong Wang (Journal of Water Process Engineering, 2024)

Influence of SiO2 size effect on multi-scale micro-nanostructure superhydrophobic Al2O3 ceramic membrane: Preparation, mechanism, application - Jiangmin Xiong; Ning Duan; Chenglong Lu; Yinfeng Zhang; Chongrui Li; Shaoxin Peng; Yongxiang Lai; Kaiwen Hu (Journal of Water Process Engineering, 2024)

Distinct toxic effects, gene expression profiles, and phytohormone responses of Polygonatum cyrtonema exposed to two different antibiotics - Guoqun Yang; Dong Jiang; Li-Jun Huang; Chuantong Cui; Runke Yang; Xin Pi; Xia Peng; Xiaofeng Peng; Jianhui Pi; Ning Li (Journal of Hazardous Materials, 2024)

Unveiling the toxic effects, physiological responses and molecular mechanisms of tobacco (Nicotiana tabacum) in exposure to organic ultraviolet filters - Dong Jiang; Guoqun Yang; Li-Jun Huang; Kebin Chen; Yangcan Tang; Xin Pi; Runke Yang; Xia Peng; Chuantong Cui; Ning Li (Journal of Hazardous Materials, 2024)

Preparation and characterization of pea protein isolate-egg white protein composite gels - Yu-Ru Zhao; Ning Peng; Chenying Wang; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Ao-Yue Sun; Xidong Ren (Food Hydrocolloids, 2024)

Assessment of nonylphenol exposure based on global urinary concentration data and its risk analysis - Jiemei Li; Hongling Zhang; Juanhua Li; Ning Qin; Qiufen Wei; Yuanyuan Li; Yang Peng; Han Li (Environmental Research, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

PLZF protein forms a complex with protein TET1 to target TCF7L2 in undifferentiated spermatogonia - Xiaomin Du; Donghui Yang; Xiuwei Yu; Yudong Wei; Wenbo Chen; Yuanxin Zhai; Fanglin Ma; Mengfei Zhang; Shicheng Wan; Yunxiang Li; Xinchun Yang; Aili Aierken; et al. (Theriogenology, 2024)

The IL-31/TRPV1 pathway mediates allergic asthma exacerbated by DINP dermal exposure in OVA-sensitized Balb/c mice - Qi Peng; Yang Wu; Yan Li; Chan Lu; Runming Yao; Siyuan Hu; Ning Ma; Shaohui Chen; Xu Yang; Ping Ma (Science of The Total Environment, 2024)

Complete decomposition of poly(ethylene terephthalate) by crude PET hydrolytic enzyme produced in Pichia pastoris - Chun-Chi Chen; Xian Li; Jian Min; Ziyin Zeng; Zhiyuan Ning; Hailin He; Xin Long; Du Niu; Rouming Peng; Xin Liu; Yu Yang; Jian-Wen Huang; et al. (Chemical Engineering Journal, 2024)

Isolation, heterologous expression, and functional determination of an iron regulated transporter (IRT) gene involved in Fe2+ transport and tolerance to Fe2+ deficiency in Vitis vinifera - Zhizhong Song; Xue Wang; Mengyuan Li; Youzheng Ning; Shengpeng Shi; Guangrong Yang; Hongxia Zhang; Meiling Tang; Bin Peng (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)
In plants, iron (Fe) regulated transporters (IRT) play important roles in uptake and transport of Fe that contributes to plant growth and development. However, biological functions of IRT transporters in fruit trees are still unknown. This study isolated 10 VvIRT genes from ‘Marselan’ grape, with varying expression levels across different tissues/organs, particularly enhanced under Fe depletion, especially in roots. Notably, VvIRT7 is the most abundantly expressed IRT gene in grape, beneficially restoring the Fe 2+ uptake defect of yeast mutant DEY1453. Furthermore, VvIRT7 showed dominant expression in the roots of irt1 /35S:: IRT7 complementation lines. Overexpressing of VvIRT7 rescued the retarded growth of irt1 knockout mutant, by increasing the fresh weight, dry weight, total root length, total root surface, lateral root numbers, total leaf chlorophyll, ACO activity, NiR activity, SDH activity, and tissue Fe concentration. This study provides insights for understanding molecular mechanisms of Fe uptake and transport in grape.

Foliar Glutamine Application Improves Grain Yield and Nutritional Quality of Field-Grown Maize (Zea mays L.) Hybrid ZD958 - Md Monirul Islam; Mahmood Ul Hassan; Muhammad Ishfaq; Farhana Alam Ripa; Faisal Nadeem; Zeeshan Ahmad; Jiuliang Xu; Peng Ning; Xuexian Li (Journal of Plant Growth Regulation, 2024)

Deterministic assembly processes shaping habitat‐specific glycoside hydrolase composition - Dan‐dan Li; Zheng Zhang; Peng Zhang; Jia‐ning Wang; Ya Liu; Yue‐zhong Li (Global Ecology and Biogeography, 2024)
Aim Glycoside hydrolases (GHs) encoded by prokaryotes play a crucial role in the degradation of carbohydrates, which is a key step in the carbon cycle. However, their global distribution remains poorly understood. Here, we conducted a comprehensive investigation of the global biogeographic patterns of prokaryotic‐encoded GHs. Location Global. Time period Present. Major taxa studied Prokaryotes. Methods We conducted a global survey of GH distribution based on 10,000 samples from the Earth Microbiome Project (EMP) and 17,923 completely sequenced prokaryotic genomes. The samples were retrieved from seven continents, covering all 17 EMP Ontology environments. We evaluated the assembly process and influencing factors of GH functional genes within prokaryotic communities, and analysed the rank abundance distributions (RADs), occupancy frequency distributions (OFDs), and taxonomic sources of GH families across various environments. Results The median number of GH genes per thousand genes encoded by global prokaryotic communities was 9.11 (7.16–11.58), with a higher GH abundance in host‐associated communities than in free‐living communities. The median number of GH families in prokaryotic communities was 105 (86–121), with fewer families but tighter functional connections between families in host‐associated communities compared to free‐living communities. In any environment, the RAD of GH families followed a lognormal model, and their OFD was bimodal, with a strong positive correlation between the two. In addition, most GH families had complex and diverse taxonomic sources across different environments. Main conclusions This study provides a panoramic view of the functional potentials for carbohydrate degradation across prokaryotic communities under diverse environmental conditions. The composition of GHs encoded by prokaryotic communities exhibits clear habitat specificity, which is driven by a combination of biotic and abiotic factors and generated through highly deterministic assembly processes.

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

A reinforcement-probability Bayesian approach for strategic bidding and market clearing for renewable energy sources with uncertainty - Liying Yu; Peng Wang; Yang Zhang; Ning Li; Rachid Cherkaoui (Journal of Cleaner Production, 2023)

Sorption behavior and mechanism of U(VI) on Tamusu clay in the presence of U(VI)-CO3 complexes - Xiaoyu Yin; Peng Wu; Shilong Shi; Yufan Zhao; Honghui Li; Feize Li; Jiali Liao; Ning Liu; Yuanyou Yang; Tu Lan (Journal of Environmental Radioactivity, 2023)

Performance of 18F-DCFPyL PET/CT in Primary Prostate Cancer Diagnosis, Gleason Grading and D'Amico Classification: A Radiomics-Based Study - Yuekai Li; Fengcai Li; Shaoli Han; Jing Ning; Peng Su; Jianfeng Liu; Lili Qu; Shuai Huang; Shiwei Wang; Xin Li; Xiang Li (Phenomics, 2023)

Association between thermal stress and cardiovascular mortality in the subtropics - Maidina Jingesi; Shuhua Lan; Jing Hu; Mengyi Dai; Suli Huang; Siyi Chen; Ning Liu; Ziquan Lv; Jiajia Ji; Xiaoheng Li; Peng Wang; Jinquan Cheng; et al. (International Journal of Biometeorology, 2023)

Nano-composite system of traditional Chinese medicine for ocular applications: molecular docking and three-dimensional modeling insight for intelligent drug evaluation - Xinyi Jiao; Xingru Peng; Xin Jin; Ning Liu; Yang Yu; Rui Liu; Zheng Li (Drug Delivery and Translational Research, 2023)

Adsorption-desorption behaviors of ciprofloxacin onto aged polystyrene fragments in aquatic environments - Xiao-Yang Liu; Ning Wang; Long-Yi Lv; Peng-Fei Wang; Wen-Fang Gao; Li Sun; Guang-Ming Zhang; Zhi-Jun Ren (Chemosphere, 2023)

Machine learning framework for intelligent aeration control in wastewater treatment plants: Automatic feature engineering based on variation sliding layer - Yu-Qi Wang; Hong-Cheng Wang; Yun-Peng Song; Shi-Qing Zhou; Qiu-Ning Li; Bin Liang; Wen-Zong Liu; Yi-Wei Zhao; Ai-Jie Wang (Water Research, 2023)

Enhancing catalytic hydrolysis activity of ZnNiAl hydrotalcite-like compounds-derived oxides using rare earth metals - Kunlin Li; Yu Tian; Xie Tang; Peng Gao; Xiao Peng; Ping Ning; Chi Wang; Fei Wang; Xin Sun; Kai Li (Journal of Cleaner Production, 2023)

Adsorption of Li+ by imprinted capacitor deionization — A new method for selective recovery of valuable lithium in acidic solutions - Ning Han; Yifei Li; Haisen Peng; Ruize Gao; Qiongqiong He; Zhenyong Miao; Keji Wan (Desalination, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Coating CoFe2O4 shell on Fe particles to increase the utilization efficiencies of Fe and peroxymonosulfate for low-cost Fenton-like reactions - Yuqing Sun; Chengbo Ma; Di Wu; Xiaomei Liu; Ning Li; Xiaobin Fan; Yang Li; Guoliang Zhang; Fengbao Zhang; Wenchao Peng (Water Research, 2023)

Potential role of fatty acid desaturase 2 in regulating peach aroma formation - Bin Peng; Zixia Gu; Yifeng Zhou; Youzheng Ning; Huanyu Xu; Gang Li; Yuan Ni; Pengpeng Sun; Zhenqiang Xie; Shengpeng Shi; Adeeba Dark; Zhizhong Song (Postharvest Biology and Technology, 2023)

Porphyrin-based hydrogen-bonded organic framework for visible light driven photocatalytic removal of U(VI) from real low-level radioactive wastewater - Peng Wu; Xiaoyu Yin; Yufan Zhao; Feize Li; Yuanyou Yang; Ning Liu; Jiali Liao; Tu Lan (Journal of Hazardous Materials, 2023)

Iron nanoparticles decorated TiO2 hollow microspheres for boosting degradation of tetracycline in a photo-Fenton catalytic system - Hongling Dai; Zhaochen Liu; Li Ou; Yue Shen; Zhihui Ning; Fengping Hu; Xiaoming Peng (Journal of Environmental Chemical Engineering, 2023)

Mobile crowdsensing framework for drive-by-based dense spatial-resolution bridge mode shape identification - Zhen Peng; Jun Li; Hong Hao; Ning Yang (Engineering Structures, 2023)

Intensive adsorption of tetracycline by cobalt oxide quantum dots-loaded mineral carbon - Ning Zhao; Qiyi Ma; Baifa Zhang; Yanfu Wei; Dong Liu; Mengyuan Li; Haoyu Li; Peng Yuan (Bioresource Technology, 2023)

Three-Dimensional Numerical Simulation Research on Discharge Characteristics of Storm-Drain Inlet in Low-Lying Areas - Ke Zhang; Jiake Li; Lizhong Ning; Weifeng Xie; Yafang Li; Zakir ullah; Kai Peng (Water Resources Management, 2023)

H2O2 activation and contaminants removal in heterogeneous Fenton-like systems - Ning Li; Xu He; Jingya Ye; Haoxi Dai; Wenchao Peng; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Shaobin Wang (Journal of Hazardous Materials, 2023)

Revealing the mechanism underlying the effects of γ-aminobutyric acid-dioscorin interactions on dioscorin structure and emulsifying properties by molecular dynamic simulations - Yun-long Chen; Hao-nan Nie; Hui Dong; Qi Gao; Xue Peng; Ning Wang; Xueling Chen; Qing-zheng Liu; Jiang-kuo Li; Xiang-bin Xu; You-lin Xue (Food Research International, 2023)

Evaluating vehicular exhaust and evaporative emissions via VOC measurement in an underground parking garage - Yajun Wu; Yan Liu; Peiji Liu; Luna Sun; Pengfei Song; Jianfei Peng; Ruikang Li; Ning Wei; Lin Wu; Ting Wang; Lina Zhang; Ning Yang; et al. (Environmental Pollution, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Prolonged fluoride exposure induces spatial-memory deficit and hippocampal dysfunction by inhibiting small heat shock protein 22 in mice - Jinge Xin; Bin Zhu; Hesong Wang; Yong Zhang; Ning Sun; Xi Cao; Liqin Zheng; Yanxi Zhou; Jing Fang; Bo Jing; Kangcheng Pan; Yan Zeng; et al. (Journal of Hazardous Materials, 2023)

Rapid reduction of aqueous Cr(VI) by oxalic acid on N-doped lignin charcoal: A significant contribution of structural defects and electronic shuttle effect - Mingxin Li; Hongling Dai; Peng Zhan; Chaoqun Tan; Zhihui Ning; Fengping Hu; Xing Xu; Xiaoming Peng (Journal of Cleaner Production, 2023)

Sustainable production of flocculant-containing bacterial cellulose composite for removal of PET nano-plastics - Hong Lu; Su Sun; Jidan Sun; Xiongyi Peng; Ning Li; Muhammad Wajid Ullah; Yanbo Zhang; Li Chen; Jiangang Zhou (Chemical Engineering Journal, 2023)

A marine lipopeptides-producing Bacillus amyloliquefaciens HY2-1 with a broad-spectrum antifungal and antibacterial activity and its fermentation kinetics study - Lin-ru Huang; Xiao-ning Ling; Shuai-ying Peng; Ming-hui Tan; Lu-qi Yan; Ying-yin Liang; Gang-hui Li; Kun-tai Li (World Journal of Microbiology and Biotechnology, 2023)

Population structure and genetic diversity of Triticum araraticum Jakubz. and Triticum timopheevii Zhuk. - Ting Peng; Xiaomei Jiang; Dinghao Wang; Minghu Zhang; Xin Liu; Ming Hao; Wei Li; Dengcai Liu; Bo Jiang; Lin Huang; Shunzong Ning; Zhongwei Yuan; et al. (Genetic Resources and Crop Evolution, 2023)

Ultrasonic-assisted self-assembly of a neodymium vanadate and hydroxylated multi-walled carbon nanotubes composite for electrochemical detection of p-nitrophenol - Ya You; Shuang-Ning Li; Jiao Zou; Ya-Nan Xin; Sui Peng; Bo Liu; Xin-Yu Jiang; Jin-Gang Yu (Process Safety and Environmental Protection, 2023)

Natural core-based laboratory analysis and comparisons of the mechanical and hydraulic characteristics of the soil skeleton of hydrate reservoirs in the South China Sea - Zhichao Liu; Guocai Gong; Yanjiang Yu; Haoxian Shi; Zhiguo Zeng; Tao Zuo; Zhun Zhang; Li Peng; Dongdong Wang; Fulong Ning (Ocean Engineering, 2023)

Poisoning mechanism of different Cd precursors on Fe-Ce/TiO2 catalyst for selective catalytic reduction of NOx with NH3 - Xiaobo Wang; Jiaqi Peng; Yue Wang; Ning Guo; Ting Li; Haijie Li; Dongdong Ren; Keting Gui (Journal of Environmental Chemical Engineering, 2023)

Insights into the enhanced performance of NiCo-LDH modified Pd/NF cathode for electrocatalytic hydrodechlorination - Jingmin Wang; Xuefeng Wei; Peipei Wang; Juan Miao; Ruichang Zhang; Ning Zhang; Xinquan Zhou; Hang Xu; Jun Zhang; Haisheng Li; Shuge Peng (Fuel, 2023)

Identification and functional characterization of caspases in turbot (Scophthalmus maximus) in response to bacterial infection - Tong Cui; Peng Liu; Xuan Chen; Zhe Liu; Beibei Wang; Chengbin Gao; Zhongyi Wang; Chao Li; Ning Yang (Fish & Shellfish Immunology, 2023)

Pericarp starch metabolism is associated with caryopsis development and endosperm starch accumulation in common wheat - Jiahui Zhuo; Ke Wang; Ning Wang; Caihong Xing; Da Peng; Xinyu Wang; Ge Qu; Caiyun Kang; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Science, 2023)

Blood redistribution preferentially protects vital organs under hypoxic stress in Pelteobagrus vachelli - Jie Li; Yao Li; Xia Liang; Zhiru Yang; Ye Peng; Yiran Zhang; Xianhui Ning; Kai Zhang; Jie Ji; Tao Wang; Guosong Zhang; Shaowu Yin (Aquatic Toxicology, 2023)

Elucidating colony bloom formation mechanism of a harmful alga Phaeocystis globosa (Prymnesiophyceae) using metaproteomics - Hua-Min Cheng; Shu-Feng Zhang; Xiao-Lian Ning; Jian-Xiang Peng; Dong-Xu Li; Hao Zhang; Kun Zhang; Lin Lin; Si-Qi Liu; Walker O. Smith; Da-Zhi Wang (Science of The Total Environment, 2023)

Selective flotation of quartz from feldspar using hydroxypropyl starch as depressant - Ning Sun; Guodong Wang; Peng Ge; Wei Sun; Longhua Xu; Honghu Tang; Li Wang (Minerals Engineering, 2023)

The role of MAPK/NF-κB-associated microglial activation in T-2 toxin-induced mouse learning and memory impairment - Na Li; Chun-Yan Yao; Jun Diao; Xiao-Ling Liu; En-Jie Tang; Qing-Song Huang; Yu-Meng Zhou; Yue-Gu Hu; Xiu-Kuan Li; Jin-Yun Long; Hua Xiao; Da-Wei Li; et al. (Food and Chemical Toxicology, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

The effectiveness of eight-years phosphorus reducing inputs on double cropping paddy: Insights into productivity and soil-plant phosphorus trade-off - Ning Su; Guixian Xie; Zhiwei Mao; Qiaorong Li; Tian Chang; Yuping Zhang; Jianwei Peng; Xiangmin Rong; Gongwen Luo (Science of The Total Environment, 2023)

Application of MXene-based materials in Fenton-like systems for organic wastewater treatment: A review - Chuanbin Wang; Jingya Ye; Lan Liang; Xiaoqiang Cui; Lingchao Kong; Ning Li; Zhanjun Cheng; Wenchao Peng; Beibei Yan; Guanyi Chen (Science of The Total Environment, 2023)

Genome-wide identification and functional characterization of inhibitor of nuclear factor-κB (IκB) kinase (IKK) in turbot (Scophthalmus maximus) - Zhe Liu; Peng Liu; Tong Cui; Xuan Chen; Beibei Wang; Chengbin Gao; Zhongyi Wang; Chao Li; Ning Yang (Fish & Shellfish Immunology, 2023)

Two pathways drive enhanced nitrogen acquisition via a complementarity effect in long-term intercropping - Yi Xing; Rui-Peng Yu; Ran An; Ning Yang; Jin-Pu Wu; Huai-Ying Ma; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Field Crops Research, 2023)

Contribution of surface plasmonic resonance to enhanced photocatalytic antibacterial performance of graphene-based two-dimensional heterojunction - Zhengao Wang; Guangyu Liu; Wei Chen; Lu Zhang; Zheng Qi; Guanghui Bai; Youzhun Fan; Chengli Liu; Cairong Xiao; Wei Li; Yunbing Chang; Guoyan Liang; et al. (Chemical Engineering Journal, 2023)

The mitigation effect of free ammonia and free nitrous acid on nitrous oxide production from the full-nitrification and partial-nitritation systems - Lai Peng; Huiling Qiu; Shengjun Li; Yifeng Xu; Chuanzhou Liang; Ning Wang; Yiwen Liu; Bing-Jie Ni (Bioresource Technology, 2023)

Research on the Purification Performance of a Floating Island System Treating the Effluent of WWTP Under Different Seasons - Zhao-xu Peng; Ning-qi Niu; Ting-mei Li; Lu-ji Yu; Li-kun Gu; Ming-hui Liu (Water, Air, & Soil Pollution, 2023)

Multi-year trends and interannual variation in ecosystem resource use efficiencies in a young mixedwood plantation in northern China - Chuan Jin; Tianshan Zha; Charles P.-A. Bourque; Peng Liu; Xin Jia; Feng Zhang; Haiqun Yu; Yun Tian; Xinhao Li; Xiaoyu Kang; Xiaonan Guo; Ning Wang (Agricultural and Forest Meteorology, 2023)

Excellent operating temperature window and H2O/SO2 resistances of Fe-Ce catalyst modified by different sulfation strategies for NH3-SCR reaction - Xiaobo Wang; Ning Guo; Jiaqi Peng; Yue Wang; Haijie Li; Dongdong Ren; Keting Gui (Environmental Science and Pollution Research, 2023)

In situ degradation of low-density polyethylene film in irrigation maize field: Thickness-dependent effect - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Rui Zhou; Jing Cao; Jing Wang; Kiprotich Wesly; Wen-Li Wang; Ning Wang; Meng Hao; Yi-Bo Wang; Hong-Yan Tao; et al. (Science of The Total Environment, 2023)

Dietary pattern interfered with the impacts of pesticide exposure by regulating the bioavailability and gut microbiota - Ai Song Chen; Dong Hui Liu; Hao Nan Hou; Jia Ning Yao; Shou Chun Xiao; Xiao Ran Ma; Pei Ze Li; Qian Cao; Xue Ke Liu; Zhi Qiang Zhou; Peng Wang (Science of The Total Environment, 2023)

A review on lignin waste valorization by catalytic pyrolysis: Catalyst, reaction system, and industrial symbiosis mode - Shaoqing Wang; Zhen Wan; Yu Han; Yan Jiao; Zhihe Li; Peng Fu; Ning Li; Andong Zhang; Weiming Yi (Journal of Environmental Chemical Engineering, 2023)

Quantitative determination of d-psicose based on flexible copper film materials and electrochemical scanning methods - Jingyu Zhang; Chengxiang Yong; Xiangchen Li; Runhao Zhu; Yongzhi Lai; Rui Peng; Ruizhi Zhao; Tianxi Yu; Jingyuan Ning; Siyi Xiong; Guohua Hui; Peng Wu (Food Chemistry, 2023)

Estimate of the degradation potentials of cellulose, xylan, and chitin across global prokaryotic communities - Dan‐dan Li; Zheng Zhang; Jia‐ning Wang; Peng Zhang; Ya Liu; Yue‐zhong Li (Environmental Microbiology, 2023)
Complex polysaccharides (e.g. cellulose, xylan, and chitin), the most abundant renewable biomass resources available on Earth, are mainly degraded by microorganisms in nature. However, little is known about the global distribution of the enzymes and microorganisms responsible for the degradation of cellulose, xylan, and chitin in natural environments. Through large‐scale alignments between the sequences released by the Earth Microbiome Project and sequenced prokaryotic genomes, we determined that almost all prokaryotic communities have the functional potentials to degrade cellulose, xylan, and chitin. The median abundances of genes encoding putative cellulases, xylanases, and chitinases in global prokaryotic communities are 0.51 (0.17–1.01), 0.24 (0.05–0.57), and 0.33 (0.11–0.71) genes/cell, respectively, and the composition and abundance of these enzyme systems are environmentally varied. The taxonomic sources of the three enzymes are highly diverse within prokaryotic communities, and the main factor influencing the diversity is the community's alpha diversity index rather than gene abundance. Moreover, there are obvious differences in taxonomic sources among different communities, and most genera with degradation potentials are narrowly distributed. In conclusion, our analysis preliminarily depicts a panorama of cellulose‐, xylan‐, and chitin‐degrading enzymatic systems across global prokaryotic communities.

A robust and 3D-printed solar evaporator based on naturally occurring molecules - Xueqian Zhang; Yu Yan; Ning Li; Peng Yang; Yiyan Yang; Gaigai Duan; Xu Wang; Yuanting Xu; Yiwen Li (Science Bulletin, 2023)

A repeated dose 28-day oral toxicity study of sodium dehydroacetate (DHA-S) in Wistar rats - Hong-ju Du; Guo-hui Tong; Jun-yu Ning; Shan Gao; Qing Yang; Ying Feng; Peng Zhang; Wei Zhang; Hai-ming Jing; Guo-jun Li (Regulatory Toxicology and Pharmacology, 2023)

Electrocatalytic hydrogenation of phenol by active sites on Pt-decorated shrimp shell biochar catalysts: Performance and internal mechanism - Xukai Lu; Jun Wang; Wenchao Peng; Ning Li; Lan Liang; Zhanjun Cheng; Beibei Yan; Gaixiu Yang; Guanyi Chen (Fuel, 2023)

C1-based biomanufacturing: Advances, challenges and perspectives - Xueqin Lv; Wenwen Yu; Chenyang Zhang; Peng Ning; Jianghua Li; Yanfeng Liu; Guocheng Du; Long Liu (Bioresource Technology, 2023)

Responses of seven wetlands carbon sources and sinks to permafrost degradation in Northeast China - Lidong Han; Changcheng Mu; Ning Jiang; Zhongqi Shen; Yihui Chang; Li Hao; Wenhong Peng (Journal of Soils and Sediments, 2023)

Does aspirin reduce the incidence, recurrence, and mortality of hepatocellular carcinoma? A GRADE-assessed systematic review and dose–response meta-analysis - Shaodi Ma; Guangbo Qu; Chenyu Sun; Haixia Liu; Yuemeng Jiang; Ning Li; Birong Wu; Juan Gao; Linya Feng; Peng Xie; Weihang Xia; Na Hyun Kim; et al. (European Journal of Clinical Pharmacology, 2023)

Fabrication of a core-shell porphyrin-based magnetic covalent organic framework for effective extraction of PCPs in a wide polarity range - Tao Ning; Siyuan Di; Zihan Li; Haokun Zhang; Zhangdi Peng; Hucheng Yang; Pin Chen; Yue Bao; Yixin Zhai; Shukui Zhu (Analytica Chimica Acta, 2023)

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

Root traits and soil nutrient and carbon availability drive soil microbial diversity and composition in a northern temperate forest - Bitao Liu; Fei Han; Peng Ning; Hongbo Li; Zed Rengel (Plant and Soil, 2022)

Comparative genomic analysis of the genus Marinomonas and taxonomic study of Marinomonas algarum sp. nov., isolated from red algae Gelidium amansii - Jian-Heng Xue; Bei-Ning Zhang; Feng Zhang; Ying-Ying Liu; Wen-Jie Wu; Zhao-Ming Wu; Yue Si; Peng-Xi Yang; Xiang Xing; Li-Hua Zhao (Archives of Microbiology, 2022)

Development and perspectives of rapid detection technology in food and environment - Xue-Xia Jia; Shuang Li; Dian-Peng Han; Rui-peng Chen; Zi-Yi Yao; Bao-an Ning; Zhi-Xian Gao; Zhen-Chuan Fan (Critical Reviews in Food Science and Nutrition, 2022)

Understanding the Sources of Heavy Metal Pollution in Ambient Air of Neighboring a Solid Waste Landfill Site - Umangi H. Mehta; Daya S. Kaul; Dane Westerdahl; Zhi Ning; Kai Zhang; Li Sun; Peng Wei; Hardik H. Gajjar; Jai D. Jeyaraman; Mansi V. Patel; Rutu R. Joshi (Aerosol Science and Engineering, 2022)

Secoiridoid glycosides from the fruits of Cornus officinalis - Xin Wang; Xiang-Jian Zhong; Na Zhou; Lin-Lin Ji; Jin-Jie Li; Ning Cai; Qing-Bo Wang; Peng-Cheng Lin; Xiao-Ya Shang (Natural Product Research, 2022)

Correction to: Construction of nitrogen vacant g-C3N4 nanosheet supported Ag3PO4 nanoparticle Z-scheme photocatalyst for improved visible-light photocatalytic activity - Xiuxiu Zhang; Guiyun Yi; Peng Li; Xiaomeng Zheng; Xuhang Shen; Kunlei Ning; Lunjian Chen; Chuanxiang Zhang; Yulong Zhang; Qi Sun (Environmental Science and Pollution Research, 2022)

Construction of nitrogen vacant g-C3N4 nanosheet supported Ag3PO4 nanoparticle Z-scheme photocatalyst for improved visible-light photocatalytic activity - Xiuxiu Zhang; Guiyun Yi; Peng Li; Xiaomeng Zheng; Xuhang Shen; Kunlei Ning; Lunjian Chen; Chuanxiang Zhang; Yulong Zhang; Qi Sun (Environmental Science and Pollution Research, 2022)

Focal white matter microstructural alteration after anthracycline-based systemic treatment in long-term breast cancer survivors: a structural magnetic resonance imaging study - Huawen Zhang; Peng Li; Tonghui Liu; Xueyuan Wang; Wei Feng; Rui Chen; Hengyang Wei; Guoqiang Li; Long Ning; Ming Zhang; Yuchen Zhang (Brain Imaging and Behavior, 2022)

Kangiella shandongensis sp. nov., a novel species isolated from saltern in Yantai, China - Li-Yang Peng; Rui Yin; Shu-Kun Gao; Hui-Ning Jiang; Xiao-Xiao Liu; Yu Ma; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2022)

Carbon limitation overrides acidification in mediating soil microbial activity to nitrogen enrichment in a temperate grassland - Qiushi Ning; Stephan Hättenschwiler; Xiaotao Lü; Paul Kardol; Yunhai Zhang; Cunzheng Wei; Chengyuan Xu; Jianhui Huang; Ang Li; Junjie Yang; Jing Wang; Yang Peng; et al. (Global Change Biology, 2021)
Higher ecosystem nitrogen (N) inputs resulting from human activities often suppress soil microbial biomass and respiration, thereby altering biogeochemical cycling. Soil acidification and carbon (C) limitation may drive these microbial responses, yet their relative importance remains elusive, which limits our understanding of the longer term effects of increasing N inputs. In a field experiment with continuous N addition at seven different rates from 0 to 50 g N m −2 year −1 over 6 years in a temperate grassland of Inner Mongolia, China, we examined the responses of soil microbial biomass and respiration to changes in soil acidity and C availability by adding lime and/or glucose to soil samples. Soil microbial biomass and respiration did only weakly respond to increasing soil pH, but increased strongly in response to higher C availability with increasing N addition rates. Soil net N immobilization increased in response to glucose addition, and soil microbial biomass increased at higher rates than microbial respiration along the gradient of previous N addition rates, both suggesting increasingly reinforced microbial C limitation with increasing N addition. Our results provide clear evidence for strong N‐induced microbial C limitation, but only little support for soil acidity effects within the initial pH range of 4.73–7.86 covered by our study. Field data support this conclusion by showing reduced plant C allocation belowground in response to N addition, resulting in soil microbial C starvation over the long term. In conclusion, soil microbial biomass and respiration under N addition were strongly dependent on C availability, most likely originating from plant belowground C inputs, and was much less affected by changes in soil pH. Our data help clarify a long‐standing debate about how increasing N input rates affect soil microbial biomass and respiration, and improve the mechanistic understanding of the linkages between ecosystem N enrichment and C cycling.

Identification of a recessive gene YrZ15-1370 conferring adult plant resistance to stripe rust in wheat-Triticum boeoticum introgression line - Minghu Zhang; Xin Liu; Ting Peng; Dinghao Wang; Dongyu Liang; Hongyu Li; Ming Hao; Shunzong Ning; Zhongwei Yuan; Bo Jiang; Xuejiao Chen; Xue Chen; et al. (Theoretical and Applied Genetics, 2021)

Surface Ligand Valency and Immunoliposome Binding: when More Is Not Always Better - Huimin Li; Jiaxing Di; Baowei Peng; Yuhong Xu; Ning Zhang (Pharmaceutical Research, 2021)

Geochemical characteristics and its geological application of over-mature Longmaxi shale gas in the northern Guizhou area, China - Yi Zhong; Peng Xia; Shitan Ning; Yong Fu; Qingguang Li; Yin Yu (Arabian Journal of Geosciences, 2021)

Tritonibacter aquimaris sp. nov. and Tritonibacter litoralis sp. nov., two novel members of the Roseobacter group isolated from coastal seawater - Na Li; Xiao-yan He; Ning-hua Liu; Tie-ji Gu; Jian Li; Yu-hui Geng; Shan Zhang; Peng Wang; Hui-hui Fu; Mei Shi; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

ZnO nanorods/Fe3O4-graphene oxide/metal-organic framework nanocomposite: recyclable and robust photocatalyst for degradation of pharmaceutical pollutants - Li Chen; Jun Peng; Fangqi Wang; Donghao Liu; Wenrong Ma; Jinmeng Zhang; Wenqing Hu; Ning Li; Pierre Dramou; Hua He (Environmental Science and Pollution Research, 2021)

Space–time variations of sea ice in Bohai Sea in the winter of 2009–2010 simulated with a coupled ocean and ice model - Rui Li; Youyu Lu; Xianmin Hu; Donglin Guo; Peng Zhao; Ning Wang; Kenneth Lee; Baiyu Zhang (Journal of Oceanography, 2021)

Theory and full-scale simulation testing of the mechanical properties of anchors under a variable lateral pressure coefficient - Tuo Wang; Jucai Chang; Zhiqiang Yin; Peng Gong; Wenbao Shi; Ning Li (Arabian Journal of Geosciences, 2021)

Potential Effect of Bioturbation by Burrowing Crabs on Sediment Parameters in Coastal Salt Marshes - Tian Xie; Peng Dou; Shanze Li; Baoshan Cui; Junhong Bai; Qing Wang; Zhonghua Ning (Wetlands, 2020)

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Erratum to: Low dose of hydroxychloroquine reduces fatality of critically ill patients with COVID-19 - Bo Yu; Chenze Li; Peng Chen; Ning Zhou; Luyun Wang; Jia Li; Hualiang Jiang; Dao-Wen Wang (Science China Life Sciences, 2020)

Low dose of hydroxychloroquine reduces fatality of critically ill patients with COVID-19 - Bo Yu; Chenze Li; Peng Chen; Ning Zhou; Luyun Wang; Jia Li; Hualiang Jiang; Dao-Wen Wang (Science China Life Sciences, 2020)

Stabilization of soil aggregate and organic matter under the application of three organic resources and biochar-based compound fertilizer - Kun Chen; Jing Peng; Jun Li; Qian Yang; Xiumei Zhan; Ning Liu; Xiaori Han (Journal of Soils and Sediments, 2020)

Transcriptome Analysis of Two Strains of Proteus mirabilis with Swarming Migration Deficiency Isolated from Patients with Urinary Tract Infection - Liang Peng; Ding-Qiang Chen; Guan-Ming Jiang; Jing-Yi Ou; Qiao Jiang; Li-Ting Zeng; Yi Xiao; Qiong-Yan Jiang; Ling Yang; Ning Sun (Current Microbiology, 2020)

Causes of slowing‐down seasonal CO 2 amplitude at Mauna Loa - Kai Wang; Yilong Wang; Xuhui Wang; Yue He; Xiangyi Li; Ralph F. Keeling; Philippe Ciais; Martin Heimann; Shushi Peng; Frédéric Chevallier; Pierre Friedlingstein; Stephen Sitch; et al. (Global Change Biology, 2020)
Changing amplitude of the seasonal cycle of atmospheric CO 2 (SCA) in the northern hemisphere is an emerging carbon cycle property. Mauna Loa (MLO) station (20°N, 156°W), which has the longest continuous northern hemisphere CO 2 record, shows an increasing SCA before the 1980s ( p 2 fertilization. This challenges the view that CO 2 fertilization is the dominant cause of emergent SCA trends at northern sites south of 40°N. The contribution of agricultural intensification on the deceleration of SCA at MLO was elusive according to land–atmosphere CO 2 flux estimated by DGVMs and atmospheric inversions. Our results also show the necessity to adequately account for changing circulation patterns in understanding carbon cycle dynamics observed from atmospheric observations and in using these observations to benchmark DGVMs.

Phytochemical constituents of the pericarps of Illicium difengpi and their anti-inflammatory activity - De-Sheng Ning; Yu-Xia Fu; Li-Yan Peng; Hui Tang; Lian-Chun Li; Xing-De Wu; Yu-Song Huang; Zheng-Hong Pan (Natural Product Research, 2020)

Enhanced adsorption of hydrophobic organic contaminants by high surface area porous graphene - Lixuan Ma; Kai Li; Chi Wang; Bo Liu; Hongbo Peng; Yi Mei; Ping Ning (Environmental Science and Pollution Research, 2020)

Global vegetation biomass production efficiency constrained by models and observations - Yue He; Shushi Peng; Yongwen Liu; Xiangyi Li; Kai Wang; Philippe Ciais; M. Altaf Arain; Yuanyuan Fang; Joshua B. Fisher; Daniel Goll; Daniel Hayes; Deborah N. Huntzinger; et al. (Global Change Biology, 2020)
Plants use only a fraction of their photosynthetically derived carbon for biomass production (BP). The biomass production efficiency (BPE), defined as the ratio of BP to photosynthesis, and its variation across and within vegetation types is poorly understood, which hinders our capacity to accurately estimate carbon turnover times and carbon sinks. Here, we present a new global estimation of BPE obtained by combining field measurements from 113 sites with 14 carbon cycle models. Our best estimate of global BPE is 0.41 ± 0.05, excluding cropland. The largest BPE is found in boreal forests (0.48 ± 0.06) and the lowest in tropical forests (0.40 ± 0.04). Carbon cycle models overestimate BPE, although models with carbon–nitrogen interactions tend to be more realistic. Using observation‐based estimates of global photosynthesis, we quantify the global BP of non‐cropland ecosystems of 41 ± 6 Pg C/year. This flux is less than net primary production as it does not contain carbon allocated to symbionts, used for exudates or volatile carbon compound emissions to the atmosphere. Our study reveals a positive bias of 24 ± 11% in the model‐estimated BP (10 of 14 models). When correcting models for this bias while leaving modeled carbon turnover times unchanged, we found that the global ecosystem carbon storage change during the last century is decreased by 67% (or 58 Pg C).

Strictly Lobar Cerebral Microbleeds Are Associated with Increased White Matter Volume - Pei-Ning Wang; Kun-Hsien Chou; Li-Ning Peng; Li-Kuo Liu; Wei-Ju Lee; Liang-Kung Chen; Ching-Po Lin; Chih-Ping Chung (Translational Stroke Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

CRISPR/Cas9 facilitates genomic editing for large-scale functional studies in pluripotent stem cell cultures - Xiao-Fei Li; Yong-Wei Zhou; Peng-Fei Cai; Wei-Cong Fu; Jin-Hua Wang; Jin-Yang Chen; Qi-Ning Yang (Human Genetics, 2019)

Genomic characterization of a novel astrovirus identified in Amur tigers from a zoo in China - Hui-Hui Zhang; Qi-Guan Qiu; Shu-Jing Liu; Wen-Qin Hu; Jie-Yu Li; Tian-Ning Liu; You-Song Peng; Xing-Yi Ge; Chao-Ting Xiao (Archives of Virology, 2019)

Optimizing the wavefield storage strategy in reflection-acoustic logging reverse-time migration - Yu-Sheng Li; Ning Li; Ye Yuan; Hong-Liang Wu; Zhou Feng; Peng Liu (Applied Geophysics, 2019)

Warming effects on soil respiration in moss-dominated crusts in the Tengger Desert, northern China - Chao Guan; Xinrong Li; Ning Chen; Peng Zhang; Changming Zhao (Plant and Soil, 2019)

Allocating assistance after a catastrophe based on the dynamic assessment of indirect economic losses - Zhengtao Zhang; Ning Li; Hong Xu; Jieling Feng; Xi Chen; Chao Gao; Peng Zhang (Natural Hazards, 2019)

The effects of temperature on human mortality in a Chinese city: burden of disease calculation, attributable risk exploration, and vulnerability identification - Xin Xu; Zuosen Chen; Xiyuan Huo; Chunping Wang; Ning Li; Xianfeng Meng; Qiang Wang; Qiyong Liu; Peng Bi; Jing Li (International Journal of Biometeorology, 2019)

Ligustroflavone reduces necroptosis in rat brain after ischemic stroke through targeting RIPK1/RIPK3/MLKL pathway - Yi-Yue Zhang; Wei-Ning Liu; Yue-Qi Li; Xiao-Jie Zhang; Jie Yang; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Paternal effects on fatty acid composition of tree peony seed oil - Qing Hao; Li-Ping Peng; Zhen Li; Si-Qi Men; Ning-Ning Tong; Qing-Yan Shu; Zheng-An Liu (Euphytica, 2019)

High Circulatory Phosphate Level Is Associated with Cerebral Small-Vessel Diseases - Chih-Ping Chung; Li-Ning Peng; Kun-Hsien Chou; Li-Kuo Liu; Wei-Ju Lee; Ching-Po Lin; Liang-Kung Chen; Pei-Ning Wang (Translational Stroke Research, 2019)

Phosphorus recovery from freeze-microwave pretreated sludge supernatant by phosphate sedimentation - Xiao Chang; Wei Zeng; Ning Li; Shuaishuai Li; Yongzhen Peng (Environmental Science and Pollution Research, 2019)

A bioactive new protostane-type triterpenoid from Alisma plantago - aquatica subsp. orientale (Sam.) Sam. - Ya-Li Wang; Jian-Chao Zhao; Jia-Hao Liang; Xiang-Ge Tian; Xiao-Kui Huo; Lei Feng; Jing Ning; Chao Wang; Bao-Jing Zhang; Gang Chen; Ning Li; Cheng-Peng Sun (Natural Product Research, 2019)

Influence of rock fractures on the amplitude of dipole-source reflected shear wave - Hao Wang; Ning Li; Cai-Zhi Wang; Hong-Liang Wu; Peng Liu; Yu-Sheng Li; Ying-Ming Liu; Ye Yuan (Applied Geophysics, 2019)

The relationship between drought activity and vegetation cover in Northwest China from 1982 to 2013 - Yelin Jiang; Ranghui Wang; Qing Peng; Xiaoquan Wu; Husen Ning; Cheng Li (Natural Hazards, 2018)

Novel alternatively spliced isoforms of MEF2A and their mRNA expression patterns in pigs - Xiao Hong Guo; Qi Zhang; Meng Li; Peng Fei Gao; Guo Qing Cao; Zhi Min Cheng; Ning Fang Zhang; Bao Yu Le; Jian Feng Liu; Xiao Jun Liu; Bu Gao Li (Journal of Genetics, 2018)

The effects of codon usage on the formation of secondary structures of nucleocapsid protein of peste des petits ruminants virus - Xiao-xia Ma; Yi-ning Wang; Xiao-an Cao; Xue-rui Li; Yong-sheng Liu; Jian-hua Zhou; Xue-peng Cai (Genes & Genomics, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Antibacterial and anti-biofilm activity of the lipid extract from Mantidis ootheca on Pseudomonas aeruginosa - Wen-dong Wang; Nan-nan Zhang; Warren Chanda; Min Liu; Syed Riaz ud Din; Yun-peng Diao; Lei Liu; Jing Cao; Xiao-li Wang; Xing-yun Li; An-hong Ning; Min Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2018)

Hsp90 regulation affects the treatment of glucocorticoid for pancreatitis-induced lung injury - Yan Zhao; Ren-Ping Xiong; Xing Chen; Ping Li; Ya-Lei Ning; Nan Yang; Yan Peng; Yu-Lin Jiang; Yuan-Guo Zhou (Molecular and Cellular Biochemistry, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

Treatment of PAH-contaminated soil using cement-activated persulfate - Fujun Ma; Qian Zhang; Bin Wu; Changsheng Peng; Ning Li; Fasheng Li; Qingbao Gu (Environmental Science and Pollution Research, 2018)

Mevastatin promotes neuronal survival against Aβ-induced neurotoxicity through AMPK activation - Edy Kornelius; Hsin-Hua Li; Chiung-Huei Peng; Hui-Wen Hsiao; Yi-Sun Yang; Chien-Ning Huang; Chih-Li Lin (Metabolic Brain Disease, 2017)

Mechanism of Lycium barbarum polysaccharides on primary cultured rat hippocampal neurons - Peng Zhao; Ning-Tian Ma; Ren-Yuan Chang; Yu-Xiang Li; Yin-Ju Hao; Wen-Li Yang; Jie Zheng; Yang Niu; Tao Sun; Jian-Qiang Yu (Cell and Tissue Research, 2017)

Orexin Directly Enhances the Excitability of Globus Pallidus Internus Neurons in Rat by Co-activating OX1 and OX2 Receptors - He-Ren Gao; Qian-Xing Zhuang; Yong-Xiao Zhang; Zhang-Peng Chen; Bin Li; Xiao-Yang Zhang; Yi-Ting Zhong; Jian-Jun Wang; Jing-Ning Zhu (Neuroscience Bulletin, 2017)

A new phenol glycoside from Physalis angulata - Cheng-Peng Sun; Xiu-Fang Nie; Ning Kang; Feng Zhao; Li-Xia Chen; Feng Qiu (Natural Product Research, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

Carbon isotopic composition and genetic types of natural gas in the Sichuan Basin, China - Jin-ning Peng; Dong-yan Wang; Guang-xiang Liu; Min Zhang; Feng-li Li (Acta Geochimica, 2017)

New Labdane diterpenes from Hedychium yunnanense with cytotoxicity and inhibitory effects on nitric oxide production - Yu-Peng Li; Si-Meng Zhao; Jun-Ju Xu; Guang-Zhi Zeng; Yan Li; Ning-Hua Tan; Ye Yang (Natural Product Research, 2016)

Sugar Industry and Improved Sugarcane Farming Technologies in China - Yang-Rui Li; Xiu-Peng Song; Jian-Ming Wu; Chang-Ning Li; Qiang Liang; Xi-Hui Liu; Wei-Zan Wang; Hong-Wei Tan; Li-Tao Yang (Sugar Tech, 2016)

The Rab1 in host cells modulates Brucella intracellular survival and binds to Brucella DnaK protein - Ning Liu; Changjiang Sun; Guimei Cui; Pan Wei; Li Yang; Wanchun Sun; Shuangxi Wang; Lin Wang; Qisheng Peng (Archives of Microbiology, 2016)

Impact of genetic polymorphisms related to clopidogrel or acetylsalicylic acid pharmacology on clinical outcome in Chinese patients with symptomatic extracranial or intracranial stenosis - Zhigang Zhao; Xingang Li; Shusen Sun; Shenghui Mei; Ning Ma; Zhongrong Miao; Ming Zhao; Shiqi Peng (European Journal of Clinical Pharmacology, 2016)

3D modeling of geological anomalies based on segmentation of multiattribute fusion - Zhi-Ning Liu; Cheng-Yun Song; Zhi-Yong Li; Han-Peng Cai; Xing-Miao Yao; Guang-Min Hu (Applied Geophysics, 2016)

Holocene high lake-levels and pan-lake period on Badain Jaran Desert - NaiAng Wang; Kai Ning; ZhuoLun Li; YiXin Wang; Peng Jia; Ling Ma (Science China Earth Sciences, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Isolation of differentially expressed sex genes in garden asparagus using suppression subtractive hybridization - Chuan-liang Deng; Ning-na Wang; Shu-fen Li; Tian-yu Dong; Xin-peng Zhao; Shao-jing Wang; Wu-jun Gao; Long-dou Lu (Journal of Plant Research, 2015)

Detection and attribution of vegetation greening trend in China over the last 30 years - Shilong Piao; Guodong Yin; Jianguang Tan; Lei Cheng; Mengtian Huang; Yue Li; Ronggao Liu; Jiafu Mao; Ranga B. Myneni; Shushi Peng; Ben Poulter; Xiaoying Shi; et al. (Global Change Biology, 2015)
The reliable detection and attribution of changes in vegetation growth is a prerequisite for the development of strategies for the sustainable management of ecosystems. This is an extraordinary challenge. To our knowledge, this study is the first to comprehensively detect and attribute a greening trend in China over the last three decades. We use three different satellite‐derived Leaf Area Index ( LAI ) datasets for detection as well as five different process‐based ecosystem models for attribution. Rising atmospheric CO 2 concentration and nitrogen deposition are identified as the most likely causes of the greening trend in China, explaining 85% and 41% of the average growing‐season LAI trend ( LAI GS ) estimated by satellite datasets (average trend of 0.0070 yr −1 , ranging from 0.0035 yr −1 to 0.0127 yr −1 ), respectively. The contribution of nitrogen deposition is more clearly seen in southern China than in the north of the country. Models disagree about the contribution of climate change alone to the trend in LAI GS at the country scale (one model shows a significant increasing trend, whereas two others show significant decreasing trends). However, the models generally agree on the negative impacts of climate change in north China and Inner Mongolia and the positive impact in the Qinghai–Xizang plateau. Provincial forest area change tends to be significantly correlated with the trend of LAI GS ( P P = 0.07) correlated with the residual of LAI GS trend, calculated as the trend observed by satellite minus that estimated by models through considering the effects of climate change, rising CO 2 concentration and nitrogen deposition, across different provinces. This result highlights the important role of China's afforestation program in explaining the spatial patterns of trend in vegetation growth.

A new daphnane diterpenoid from Excoecaria venenata with inhibitory effect on human leukaemia HL-60 cells - De-Sheng Ning; Li-Yan Peng; Shi-Hong Lv; Dian-Peng Li; Zheng-Hong Pan (Natural Product Research, 2015)

Glial fibrillary acidic protein promoters direct adenovirus early 1A gene and human telomerase reverse transcriptase promoters direct sodium iodide symporter expression for malignant glioma radioiodine therapy - Wei Li; Jian Tan; Peng Wang; Ning Li; Chengxia Li (Molecular and Cellular Biochemistry, 2015)

Overexpression of MicroRNA-122 Re-sensitizes 5-FU-Resistant Colon Cancer Cells to 5-FU Through the Inhibition of PKM2 In Vitro and In Vivo - Jinxia He; Ganfeng Xie; Jingtao Tong; Yonghai Peng; Haihui Huang; Jianjun Li; Ning Wang; Houjie Liang (Cell Biochemistry and Biophysics, 2014)

Hsa-miR-1246, hsa-miR-320a and hsa-miR-196b-5p inhibitors can reduce the cytotoxicity of Ebola virus glycoprotein in vitro - MiaoMiao Sheng; Ying Zhong; Yang Chen; JianChao Du; XiangWu Ju; Chen Zhao; GuiGen Zhang; LiFang Zhang; KangTai Liu; Ning Yang; Peng Xie; DangSheng Li; et al. (Science China Life Sciences, 2014)

Role of Unfolded Protein Response in Affecting Osteoblast Differentiation Induced by Fluoride - Xi-ning Li; Peng Lv; Zhi Sun; Guang-sheng Li; Hui Xu (Biological Trace Element Research, 2014)

Effects of lipopolysaccharide-induced inflammation on the interstitial cells of Cajal - Jia Wei; Ning Li; Xue Xia; Xuyong Chen; Fei Peng; Gail E. Besner; Jiexiong Feng (Cell and Tissue Research, 2014)

A new triterpenoid saponin from the root of Croton lachnocarpus Benth. - Zheng-Hong Pan; De-Sheng Ning; Jin-Lei Liu; Bo Pan; Dian-Peng Li (Natural Product Research, 2014)

A Quantitative Method to Control and Adjust the Accuracy of Adaptive Grid Depth Modeling - Zhang Lihua; Jia Shuaidong; Peng Rencan; Dong Jian; Li Ning (Marine Geodesy, 2013)

Discovery of indeno[1,2- $$c$$ c ]quinoline derivatives as dual topoisomerases I/II inhibitors: Part 3 - Chih-Hua Tseng; Cherng-Chyi Tzeng; Chiao-Li Yang; Pei-Jung Lu; Yu-Peng Liu; Hui-Ling Chen; Chien-Yu Chen; Chia-Ning Yang; Yeh-Long Chen (Molecular Diversity, 2013)

Genes encoding the production of extracellular polysaccharide bioflocculant are clustered on a 30-kb DNA segment in Bacillus licheniformis - Shan Yan; Na Wang; Zhen Chen; Yuanpeng Wang; Ning He; Yajuan Peng; Qingbiao Li; Xu Deng (Functional & Integrative Genomics, 2013)

Role of Endoplasmic Reticulum Stress in Aberrant Activation of Fluoride-Treated Osteoblasts - Yu-lai Zhou; Hong-yan Shi; Xi-ning Li; Peng Lv; Guang-sheng Li; Qin-yi Liu; Hui Xu (Biological Trace Element Research, 2013)

Sequence analysis of the whole genome of a recombinant Marek’s disease virus strain, GX0101, with a reticuloendotheliosis virus LTR insert - Shuai Su; Ning Cui; Aijun Sun; Yanpeng Li; Jiabo Ding; Zimeng Chen; Peng Zhao; Zhizhong Cui (Archives of Virology, 2013)

DNA methylation alterations of upland cotton (Gossypium hirsutum) in response to cold stress - Hong Hong Fan; Jun Wei; Ting Chun Li; Zheng Peng Li; Ning Guo; Yong Ping Cai; Yi Lin (Acta Physiologiae Plantarum, 2013)

miR-30a downregulation aggravates pressure overload-induced cardiomyocyte hypertrophy - Xuesong Yin; Chenghai Peng; Wenhu Ning; Chunyan Li; Zhongqiao Ren; Jihong Zhang; Han Gao; Kan Zhao (Molecular and Cellular Biochemistry, 2013)

Isolation and genomic characterization of three enterovirus 90 strains in Shandong, China - Zexin Tao; Ning Cui; Aiqiang Xu; Yao Liu; Lizhi Song; Yan Li; Haiyan Wang; Feng Ji; Peng Chen; Yanyan Song (Archives of Virology, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

A meta-analysis of the relationship between glutathione S-transferases gene polymorphism and hepatocellular carcinoma in Asian population - Jie Chen; Liang Ma; Ning-Fu Peng; Shi-Jun Wang; Le-Qun Li (Molecular Biology Reports, 2012)

Fraction characteristics of rare earth elements in the surface sediment of Bohai Bay, North China - Yayan Xu; Jinming Song; Liqin Duan; Xuegang Li; Huamao Yuan; Ning Li; Peng Zhang; Ying Zhang; Sisi Xu; Mo Zhang; Xiaodan Wu; Xuebo Yin (Environmental Monitoring and Assessment, 2012)

Triterpenoid saponins from Ilex mamillata C.Y. Wu ex C.J. Tseng - Che Yan-Yun; Zhang Liang; Li Ning; Zeng Ke-Wu; Tu Peng-Fei (Natural Product Research, 2012)

Spatiotemporal Variations in Nitrous Oxide Emissions from an Open Fen on the Qinghai–Tibetan Plateau: a 3-Year Study - Huai Chen; Yanfen Wang; Ning Wu; Dan Zhu; Wei Li; Yongheng Gao; Qiu’an Zhu; Gang Yang; Changhui Peng (Water, Air, & Soil Pollution, 2012)

The return periods and risk assessment of severe dust storms in Inner Mongolia with consideration of the main contributing factors - Xueqin Liu; Ning Li; Wei Xie; Jidong Wu; Peng Zhang; Zhonghui Ji (Environmental Monitoring and Assessment, 2012)

Different effects of omega-3 fatty acids on the cell cycle in C2C12 myoblast proliferation - Yunqian Peng; Yu Zheng; Yunsheng Zhang; Jie Zhao; Fei Chang; Tianyu Lu; Ran Zhang; Qiuyan Li; Xiaoxiang Hu; Ning Li (Molecular and Cellular Biochemistry, 2012)

Molecular Cloning and Expression Analysis of Porcine Ghrelin O-Acyltransferase - Tonghui Lin; Qingyong Meng; Dandan Sui; Dezhi Peng; Yang Li; Xiaofang Liu; Longfei Xie; Ning Li (Biochemical Genetics, 2011)

Genetic Linkage Mapping and Analysis of Muscle Fiber-Related QTLs in Common Carp (Cyprinus carpio L.) - Yan Zhang; Peng Xu; Cuiyun Lu; Youyi Kuang; Xiaofeng Zhang; Dingchen Cao; Chao Li; Yumei Chang; Ning Hou; Hengde Li; Shu Wang; Xiaowen Sun (Marine Biotechnology, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

Efficacy of a novel endotoxin adsorber polyvinylidene fluoride fiber immobilized with L-serine ligand on septic pigs - Jian-ping Gao; Man Huang; Ning Li; Peng-fei Wang; Huan-lin Chen; Qiu-ping Xu (Journal of Zhejiang University-SCIENCE B, 2011)

Analysis of correlation between blood biochemical indicators and bone mineral density of post-menopausal women - Shun-zhi Liu; Li-fang Tian; Peng Xu; Gui-hua Zhuang; Fang Zheng; Juan Tian; Qi-Lan Ning; Bo-Feng Zhu; She-Min Lu; Hong Yan (Molecular Biology Reports, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

Tumor-inhibitory and liver-protective effects of Phellinus igniarius extracellular polysaccharides - Wei Dong; Li Ning; Wei-dong Lu; Cui-cui Li; Rui-peng Chen; Xiao-ning Jia; Lin Wang; Li-zhong Guo (World Journal of Microbiology and Biotechnology, 2009)

Analysis of dynamics and driving factors of wetland landscape in Zoige, Eastern Qinghai-Tibetan Plateau - Pengfei Qiu; Ning Wu; Peng Luo; Zuyuan Wang; Maihe Li (Journal of Mountain Science, 2009)

Improvement of the multiple-stress tolerance of an ethanologenic Saccharomyces cerevisiae strain by freeze-thaw treatment - Pingying Wei; Zilong Li; Yuping Lin; Peng He; Ning Jiang (Biotechnology Letters, 2007)

Identification and functional characterization of a leucine-rich repeat receptor-like kinase gene that is involved in regulation of soybean leaf senescence - Xiao-Ping Li; Rui Gan; Peng-Li Li; Yuan-Yuan Ma; Li-Wen Zhang; Ren Zhang; Yong Wang; Ning Ning Wang (Plant Molecular Biology, 2006)

(R)-Oxynitrilase-catalysed synthesis of chiral silicon-containing aliphatic (R)-ketone-cyanohydrins - Ning Li; Min-Hua Zong; Chen Liu; Hua-Song Peng; Hua-Chang Wu (Biotechnology Letters, 2003)